Non-aqueous alkali metal storage element and positive electrode coating solution
By uniformly dispersing single-layer carbon nanotubes in the positive and negative active material layers of the non-aqueous alkali metal power storage element, and optimizing the electrolyte composition and process parameters, the resistance problems caused by carbon nanotubes in the electrode are solved, and high energy density, high output characteristics and high durability are achieved.
Patent Information
- Application Number
- CN202180053447.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-18
- Filing Date
- 2021-10-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-10-19
AI Technical Summary
In the prior art, when the non-aqueous alkali metal electric storage element contains carbon nanotubes in the active material layer, it is difficult to reduce the diffusion resistance of ions and suppress the rise of electron migration resistance at high temperatures. At the same time, there are shortcomings in the positive electrode coating liquid to take into account both the increase in energy density and the improvement of output characteristics.
Using a positive electrode coating liquid containing a single layer of carbon nanotubes, the carbon nanotubes are uniformly dispersed in the positive electrode and the negative electrode active material layers and controlled their content to optimize the bulk density and conductivity of the electrodes, and further adjust the electrolyte composition and process parameters to suppress the rise of resistance at high temperature and high voltage.
The high energy density and high output characteristics of non-aqueous alkali metal power storage components are achieved, while maintaining low resistance and high durability in high temperature and high voltage environments, improving the overall performance of power storage components.
Smart Images

Figure CN116114041B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a non-aqueous alkali metal energy storage device, a positive electrode coating solution, and the like. Background Art
[0002] In recent years, from the perspective of effectively utilizing energy in order to protect the earth's environment and save resources, power stabilization systems or midnight power storage systems for wind power generation, distributed power storage systems for households based on solar power generation technology, and power storage systems for electric vehicles have attracted attention. The first requirement for batteries used in these power storage systems is high energy density. As a powerful supplement to high-energy density batteries that can meet such requirements, the development of lithium-ion batteries has been actively promoted. The second requirement is high output characteristics. For example, in a combination of a high-efficiency engine and a power storage system (such as a hybrid electric vehicle), or a combination of a fuel cell and a power storage system (such as a fuel cell electric vehicle), a power storage system that exhibits high output discharge characteristics during acceleration is required. At present, as high-output power storage devices, double-layer capacitors, nickel-hydrogen batteries, etc. are being developed.
[0003] In a double-layer capacitor, when activated carbon is used in the electrode, it has an output characteristic of about 0.5 to 1 kW / L. This double-layer capacitor has not only high output characteristics, but also high durability (cycle characteristics and high-temperature storage characteristics), and is considered to be the best device in the above-mentioned field requiring high output. However, its energy density is only about 1 to 5 Wh / L, so it is necessary to further improve the energy density.
[0004] Nickel-metal hydride batteries commonly used in hybrid electric vehicles currently have high output comparable to that of electric double layer capacitors and have an energy density of about 160 Wh / L. However, research is being actively conducted to further improve the energy density and output characteristics and to improve durability (especially stability at high temperatures).
[0005] In lithium-ion batteries, research has also been conducted towards high output. For example, a lithium-ion battery with a high output of more than 3kW / L has been developed when the depth of discharge (i.e., the ratio of the discharge amount to the discharge capacity of the storage element (%)) is 50%. However, its energy density is less than 100Wh / L, and the high energy density, which is the biggest feature of lithium-ion batteries, is deliberately suppressed by the design. In addition, its durability (cycle characteristics and high-temperature storage characteristics) is inferior to that of double-layer capacitors. Therefore, for such lithium-ion batteries, in order to make them have practical durability, they are used in a range narrower than the range of 0 to 100% depth of discharge. Since the capacity of lithium-ion batteries that can be actually used will become smaller, research is actively conducted to further improve durability.
[0006] As mentioned above, there is a strong demand for the practical application of storage elements that have high energy density, high output characteristics and high durability. However, the above-mentioned existing storage elements have both advantages and disadvantages, so a new storage element that fully meets these technical requirements is required. As a powerful supplement to it, the storage element called lithium ion capacitor has attracted attention and has been actively developed. Lithium ion capacitor is a type of storage element using a non-aqueous electrolyte containing lithium salt (hereinafter also referred to as "non-aqueous alkali metal storage element"), which is a storage element that is charged and discharged by performing a non-Faraday reaction based on the adsorption and desorption of anions similar to double-layer capacitors at a positive electrode at about 3V or more, and performing a Faraday reaction based on the absorption and release of lithium ions similar to lithium ion batteries at the negative electrode.
[0007] The electrode materials and characteristics commonly used in the above-mentioned storage elements are summarized. Usually, when materials such as activated carbon are used in the electrode, high output and high durability can be obtained when charging and discharging are performed by adsorption and desorption of ions on the surface of the activated carbon (non-Faraday reaction), but the energy density is reduced (for example, 1 times). On the other hand, when oxides or carbon materials are used in the electrode, when charging and discharging are performed by Faraday reaction, the energy density is increased (for example, 10 times that of non-Faraday reaction using activated carbon), but there are problems with durability and output characteristics.
[0008] As a combination of these electrode materials, the electric double layer capacitor is characterized in that activated carbon (energy density 1 times) is used in the positive electrode and the negative electrode, and both the positive and negative electrodes are charged and discharged by non-Faraday reactions. Therefore, although it has high output and high durability, it has a low energy density (1 times the positive electrode × 1 times the negative electrode = 1).
[0009] The characteristics of lithium-ion secondary batteries are that lithium transition metal oxides (10 times the energy density) are used in the positive electrode and carbon materials (10 times the energy density) are used in the negative electrode. Both the positive and negative electrodes are charged and discharged through Faraday reactions. Therefore, although they have high energy density (10 times the positive electrode × 10 times the negative electrode = 100), there are problems with output characteristics and durability. In addition, in order to meet the high durability required by hybrid electric vehicles, the depth of discharge must be limited. In lithium-ion secondary batteries, only 10 to 50% of their energy can be used.
[0010] The characteristic of lithium-ion capacitors is that activated carbon (1 times the energy density) is used in the positive electrode, carbon material (10 times the energy density) is used in the negative electrode, and charging and discharging are performed by non-Faraday reaction at the positive electrode and charging and discharging are performed by Faraday reaction at the negative electrode. Therefore, it is an asymmetric capacitor that has the characteristics of both double-layer capacitors and lithium-ion secondary batteries. The characteristic of lithium-ion capacitors is that despite having high output and high durability, they have high energy density (1 times the positive electrode × 10 times the negative electrode = 10), and there is no need to limit the depth of discharge like lithium-ion secondary batteries.
[0011] Regarding the further high output and high durability of lithium ion capacitors, for example, in Patent Document 1, in order to achieve the high output of lithium ion capacitors, a negative electrode is described, which forms a coating composed of carbon nanotubes and carboxymethyl cellulose on the surface of the negative electrode active material, and the mixing amount is carboxymethyl cellulose / carbon nanotubes = 1.5 to 7.0 in terms of mass ratio. In Patent Document 2, in order to improve the energy density, a lithium ion capacitor having a positive electrode composed of graphene and carbon nanotubes, and a negative electrode is described. Patent Document 3 describes a positive electrode precursor that can promote the decomposition of alkali metal compounds contained in the positive electrode precursor, and has high capacity and high output. Patent Document 4 describes a technology for containing phosphate ester amide in a non-aqueous electrolyte in order to suppress the decomposition of LiPF6 at high temperatures. In Patent Document 5, in order to improve the energy density, a lithium ion capacitor having a positive electrode composed of graphene and carbon nanotubes, and a negative electrode is described. Patent document 6 describes a positive electrode precursor that can promote the decomposition of alkali metal compounds contained in the positive electrode precursor, and has high capacity and high output. Patent document 7 describes an electrode for a storage device, which includes at least one active material selected from the group consisting of carbon nanotubes, activated carbon, hard carbon, graphite, graphene and carbon nanotubes, an ionic liquid, and a three-dimensional mesh structure porous body. Patent document 8 describes an electrolyte containing a lithium fluorophosphate additive, a sulfone ester additive, and a copper compound, and a storage element. Patent document 9 describes a positive electrode that can promote the decomposition of alkali metal compounds contained in the positive electrode, and has high capacity and high output.
[0012] Regarding the coating liquid for forming the positive electrode active material layer of the lithium ion capacitor (hereinafter also referred to as "positive electrode coating liquid"), for example, Patent Document 10 proposes a positive electrode coating liquid, which contains a carbon material, an alkali metal compound, and polyacrylic acid as a binding material, and the time change of the thixotropic index is within a certain range. Patent Document 11 proposes a carbon nanotube dispersion liquid containing a dispersion material, a solvent, and carbon nanotubes with specific physical properties; and a non-aqueous electrolyte secondary battery containing the above dispersion liquid in at least one of the positive and negative electrodes. Patent Document 12 discloses a carbon nanotube dispersion liquid containing a polymer dispersion material, an organic solvent and carbon nanotubes and having specific viscosity characteristics.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Publication No. 2015-156293
[0016] Patent Document 2: International Publication No. 2018 / 147080
[0017] Patent Document 3: International Publication No. 2017 / 126687
[0018] Patent Document 4: International Publication No. 2013 / 187073
[0019] Patent Document 5: International Publication No. 2018 / 147080
[0020] Patent Document 6: International Publication No. 2017 / 126687
[0021] Patent Document 7: International Publication No. 2013 / 73526
[0022] Patent Document 8: International Publication No. 2017 / 038406
[0023] Patent Document 9: International Publication No. 2017 / 126687
[0024] Patent Document 10: International Publication No. 2019 / 156090
[0025] Patent Document 11: International Publication No. 2021 / 080006
[0026] Patent Document 12: International Publication No. 2020 / 129872
[0027] Non-patent literature
[0028] Non-patent document 1: EP Barrett, LG Joyner and P. Halenda, "The Determination of Pore Volume and Area Distributions in PorousSubstances.I.ComputationsfromNitrogen Isotherms", J.Am.Chem.Soc., (1951), 73(1), pp.373-380
[0029] Non-patent document 2: BC Lippens and JH de Boer, "Studies on Pore Systems in Catalysts", J. Catalysis, (1965), 4, pp. 319-323
[0030] Non-patent document 3: RS Mikhail, S. Brunauer and E E Bodor, "Investigations of a Complete Pore Structure Analysis" J. Colloid Interface Sci., (1968), 26, pp. 45-53 Summary of the invention
[0031] Problems to be solved by the invention
[0032] However, none of the prior art documents discloses reducing ion diffusion resistance and suppressing an increase in electron transfer resistance at high temperatures in a non-aqueous alkali metal energy storage device including carbon nanotubes in its active material layer.
[0033] Furthermore, none of the prior art documents describes achieving both improvement in energy density and improvement in output characteristics in a positive electrode coating solution containing carbon nanotubes.
[0034] In view of the above-mentioned current situation, an object of one aspect of the present disclosure is to provide a non-aqueous alkali metal energy storage device that can reduce ion diffusion resistance and suppress an increase in electron transfer resistance at high temperatures.
[0035] Another object of the present disclosure is to provide a positive electrode coating solution containing carbon nanotubes, which contributes to providing a non-aqueous alkali metal storage element having high energy density and high output.
[0036] Means for solving problems
[0037] Examples of embodiments of the present disclosure are listed in the following items [1] to
[12] . [1]
[0039] A non-aqueous alkali metal storage element comprises a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte containing alkali metal ions, wherein:
[0040] The positive electrode comprises a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material with activated carbon as a main component and carbon nanotubes,
[0041] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer provided on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and carbon nanotubes.
[0042] The carbon nanotubes are single-walled carbon nanotubes having a bundle structure with an average fiber diameter of 5 nm to 20 nm. [2]
[0044] The nonaqueous alkali metal storage element according to item 1, wherein, when the content of the carbon nanotubes contained in the positive electrode active material layer is A (mass %) and the content of the carbon nanotubes contained in the negative electrode active material layer is B (mass %),
[0045] 0.010≤A≤0.200,
[0046] 0.003≤B≤0.120, and
[0047] A>B. [3]
[0049] The nonaqueous alkali metal energy storage device according to item 1 or 2, wherein the carbon nanotubes cover the positive electrode active material and / or the surface of the positive electrode active material in a mesh shape. [4]
[0051] The nonaqueous alkali metal energy storage device according to any one of items 1 to 3, wherein the carbon nanotubes bridge the positive electrode active material and / or the positive electrode active materials. [5]
[0053] The nonaqueous alkali metal energy storage device according to any one of items 1 to 4, wherein the carbon nanotubes cover the negative electrode active material and / or the surface of the negative electrode active material in a mesh shape. [6]
[0055] The nonaqueous alkali metal energy storage device according to any one of items 1 to 5, wherein the carbon nanotubes bridge the negative electrode active material and / or the negative electrode active materials with each other. [7]
[0057] The nonaqueous alkali metal energy storage device according to any one of items 1 to 6, wherein the amount of copper element contained in the positive electrode active material layer is 1 ppm to 500 ppm. [8]
[0059] The nonaqueous alkali metal storage device according to any one of items 1 to 7, wherein the nonaqueous electrolyte solution comprises a phosphate ester amide represented by the following general formula (1):
[0060] [Chemistry 1]
[0061]
[0062] {wherein, m represents an integer of 1 or 2, R 1 and R 2 Each of R is independently a branched or straight-chain alkyl group having 1 to 6 carbon atoms, or a branched or straight-chain hydrocarbon group having an unsaturated bond. 1 and R 2 may independently have a substituent selected from the group consisting of an alkylthio group and a saturated heterocyclic group, R 1 With R 2 They can bond to each other to form a 5- to 8-membered ring structure. 3 represents a branched or linear alkyl group having 1 to 6 carbon atoms or a branched or linear fluorine-containing alkyl group having 1 to 6 carbon atoms}. [9]
[0064] A power storage module comprising the nonaqueous lithium power storage element according to any one of items 1 to 8.
[10]
[0066] A power storage module as described in Item 9, wherein the above-mentioned power storage module is assembled into a system selected from the group consisting of a power regeneration assist system, a power load balancing system, an uninterruptible power supply system, a contactless power supply system, an energy harvesting system, a natural energy storage system, an electric power steering system, an emergency power supply system, a hub motor system, an idle stop system, an electric vehicle, a plug-in hybrid vehicle, an electric two-wheeler, a fast charging system and a smart grid system.
[11]
[0068] A positive electrode coating solution comprises activated carbon, an alkali metal compound, and a single-layer carbon nanotube, wherein:
[0069] The amount of solid content is 35.0 mass % or more and 50.0 mass % or less relative to the total mass of the positive electrode coating liquid.
[0070] Satisfy either or both of the following (a) and (b).
[0071] (a) At a shear rate of 10 s -1 More than 1000s -1 In the range below, the viscosity decreases monotonically with increasing shear rate.
[0072] (b) At a shear rate of 100 s -1 More than 1000s -1 In the following range, the ratio X / Y of the maximum value X (mPa·s) of the viscosity to the minimum value Y (mPa·s) of the viscosity is 1.0 or more and 4.0 or less.
[12]
[0074] The positive electrode coating solution according to item 11, wherein the amount of the single-walled carbon nanotubes contained in the positive electrode coating solution is 0.010 mass % or more and 0.200 mass % or less based on the total mass of the solid content contained in the positive electrode coating solution.
[0075] Effects of the Invention
[0076] According to one aspect of the present disclosure, a non-aqueous alkali metal storage element is provided, which can reduce the diffusion resistance of ions and suppress the increase of electron migration resistance at high temperature. On the other hand, according to the present disclosure, a positive electrode coating liquid is provided, which is a positive electrode coating liquid containing carbon nanotubes, which helps to provide a non-aqueous alkali metal storage element with high energy density and high output. A positive electrode coating liquid containing single-layer carbon nanotubes and taking into account dispersibility and viscosity stability can be produced, thereby reducing the diffusion resistance of ions, increasing the stacking density of the electrode, and increasing the conductivity of the electrode after applying the coating liquid. In addition, by controlling the content of single-layer carbon nanotubes in the positive and negative electrodes, a non-aqueous alkali metal storage element can be provided, which suppresses the increase of electron migration resistance in an environment above 80°C and above 4.1V, has high input-output characteristics and a high pre-doping amount, and has small capacity degradation and resistance increase at high temperature and high voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a SEM image of negative electrode 1-5 in Example 1 photographed at a magnification of 20,000 times.
[0078] Figure 2 This is a SEM image of the positive electrode precursor 1-9 in the example taken at a magnification of 20,000 times.
[0079] Figure 3 It is the viscosity curve of the positive electrode coating liquid 4-1.
[0080] Figure 4 This is the viscosity curve of positive electrode coating liquid 4-4.
[0081] Figure 5 It is the viscosity curve of positive electrode coating solution 4-7.
[0082] Figure 6 It is the viscosity curve of positive electrode coating solution 4-10. DETAILED DESCRIPTION
[0083] The embodiments of the present disclosure are described in detail below, but the present disclosure is not limited to the embodiments. The upper limit and the lower limit in each numerical range of the present disclosure can be arbitrarily combined to form any numerical range.
[0084] 《Non-aqueous alkali metal energy storage device》
[0085] The non-aqueous alkali metal storage element disclosed in the present invention has a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte as main components. As the non-aqueous electrolyte, a solution in which alkali metal ions are dissolved in an organic solvent is used.
[0086] <Positive electrode>
[0087] The positive electrode has a positive electrode current collector and a positive electrode active material layer provided on one or both surfaces of the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material having activated carbon as a main component and carbon nanotubes.
[0088] As described below, in the assembly process of the storage element, it is preferred to pre-dope the negative electrode with alkali metal ions. As the pre-doping method, it is preferred to assemble the storage element using a positive electrode precursor, a negative electrode, a separator, an outer body and a non-aqueous electrolyte containing an alkali metal compound, and then apply a voltage between the positive electrode precursor and the negative electrode. In this case, the alkali metal compound can be contained in the positive electrode precursor in any manner. For example, the alkali metal compound can be present between the positive electrode collector and the positive electrode active material layer, can be present on the surface of the positive electrode active material layer, or can be present in the positive electrode active material layer. The alkali metal compound is preferably contained in the positive electrode active material layer formed on the positive electrode collector of the positive electrode precursor. In such a manner, along with the pre-doping of alkali metal ions into the negative electrode, pores are formed in the positive electrode active material layer, and the effective area of the positive electrode active material layer is increased. In this specification, the positive electrode before the alkali metal doping process is defined as a "positive electrode precursor", and the positive electrode after the alkali metal doping process is defined as a "positive electrode".
[0089] [Positive electrode active material layer]
[0090] The positive electrode active material layer contains a positive electrode active material having activated carbon as a main component and carbon nanotubes. The positive electrode active material layer preferably further contains an alkali metal compound. In addition to these components, the positive electrode active material layer may further contain optional components described below as needed.
[0091] (Positive electrode active material)
[0092] The positive electrode active material contains activated carbon as a main component. "Active material contained as a main component" refers to the component with the largest mass % in the material (positive electrode active material) that can embed and deintercalate alkali metal ions. In addition to activated carbon, the positive electrode active material may further contain graphene, conductive polymers, and lithium transition metal oxides.
[0093] There is no particular restriction on the type of activated carbon and its raw materials. In order to achieve both high input-output characteristics and high energy density, it is preferred to optimally control the pores of the activated carbon. Specifically, the diameter of the activated carbon calculated by the BJH method is Above The mesopore volume of the pores below is set to V1 (cc / g), and when the micropore volume of the pores with a diameter less than is calculated by the MP method and set to V2 (cc / g),
[0094] (1) In order to obtain high input-output characteristics, it is preferable to satisfy 0.3 < V1 ≤ 0.8 and 0.5 ≤ V2 ≤ 1.0, and the specific surface area measured by the BET method is 1,500 m 2 / g or more and 3,000 m 2 / g or less of activated carbon (hereinafter also referred to as activated carbon 1); in addition,
[0095] (2) In order to obtain high energy density, it is preferable to satisfy 0.8 < V1 ≤ 2.5 and 0.8 < V2 ≤ 3.0 and the specific surface area measured by the BET method is 2,300 m 2 / g or more and 4,000 m 2 / g or less of activated carbon (hereinafter also referred to as activated carbon 2).
[0096] The BET specific surface area, mesopore volume, micropore volume, and average pore diameter of the active material are the values obtained by the following methods. The sample is vacuum-dried at 200 °C for one day and night, and the isotherm of adsorption and desorption is measured using nitrogen as the adsorbed substance. Using the adsorption-side isotherm obtained here, the BET specific surface area is calculated by the BET multi-point method or the BET single-point method, the mesopore volume is calculated by the BJH method, and the micropore volume is calculated by the MP method. The BJH method is a calculation method commonly used in the analysis of mesopores and was proposed by Barrett, Joyner, Halenda, etc. (Non-Patent Document 1). The MP method refers to a method of using the "t-Plot method" (Non-Patent Document 2) to obtain the micropore volume, micropore area, and micropore distribution, and is a method designed by R.S. Mikhail, Brunauer, and Bodor (Non-Patent Document 3). In addition, the average pore diameter is the value obtained by dividing the total pore volume per unit mass of the sample by the above BET specific surface area, and the total pore volume per unit mass is obtained by measuring the equilibrium adsorption amount of nitrogen at each relative pressure at liquid nitrogen temperature.
[0097] (Activated carbon 1)
[0098] From the perspective of increasing the input-output characteristics after assembling the positive electrode material into the storage element, the mesopore volume V1 of the activated carbon 1 is preferably greater than 0.3cc / g. From the perspective of suppressing the reduction of the stacking density of the positive electrode, V1 is preferably less than 0.8cc / g. V1 is more preferably 0.35cc / g or more and 0.7cc / g or less, and further preferably 0.4cc / g or more and 0.6cc / g or less. In order to increase the specific surface area and capacity of the activated carbon, the micropore volume V2 of the activated carbon 1 is preferably 0.5cc / g or more. From the perspective of suppressing the volume of the activated carbon, increasing the density as an electrode, and increasing the capacity per unit volume, V2 is preferably less than 1.0cc / g. V2 is more preferably 0.6cc / g or more and 1.0cc / g or less, and further preferably 0.8cc / g or more and 1.0cc / g or less. The ratio of the mesopore volume V1 to the micropore volume V2 (V1 / V2) is preferably in the range of 0.3≤V1 / V2≤0.9. That is, from the perspective of increasing the ratio of the amount of mesopores to the amount of micropores to the extent that the output characteristics can be suppressed while maintaining high capacity, V1 / V2 is preferably 0.3 or more. On the other hand, from the perspective of increasing the ratio of the amount of micropores to the amount of mesopores to the extent that the capacity can be suppressed while maintaining high output characteristics, V1 / V2 is preferably 0.9 or less. A more preferred range of V1 / V2 is 0.4≤V1 / V2≤0.7, and a further preferred range of V1 / V2 is 0.55≤V1 / V2≤0.7.
[0099] From the viewpoint of maximizing the output of the obtained electric storage element, the average pore diameter of the activated carbon 1 is preferably More preferably Above, most preferably In addition, from the perspective of maximizing the capacity, the average pore size of the activated carbon 1 is preferably The BET specific surface area of the activated carbon 1 is preferably 1,500 m 2 / g above 3,000m 2 / g or less, more preferably 1,500m 2 / g or more 2,500m 2 / g or less. BET specific surface area is 1,500m 2 / g or more, a good energy density is easily obtained, while a BET specific surface area of 3,000 m 2 When the content of the binder is 0.1477 W / g or less, it is not necessary to add a large amount of binder to ensure the strength of the electrode, so the performance per unit volume of the electrode is improved.
[0100] The activated carbon 1 having the above characteristics can be obtained, for example, using the raw materials and treatment methods described below. The carbon source used as the raw material of the activated carbon 1 is not particularly limited. For example, plant raw materials such as wood, wood powder, coconut shells, by-products of pulp production, bagasse, and waste molasses can be cited; fossil raw materials such as peat, charcoal, lignite, bituminous coal, anthracite, petroleum distillation residue components, petroleum asphalt, coke, and coal tar; phenol resins, vinyl chloride resins, vinyl acetate resins, melamine resins, urea resins, resorcinol resins, celluloids, epoxy resins, polyurethane resins, polyester resins, polyamide resins and other synthetic resins; synthetic rubbers such as polybutene, polybutadiene, and polychloroprene; other synthetic woods, synthetic pulps, and the like, and their carbonized products. Among these raw materials, plant raw materials such as coconut shells and wood powder and their carbonized products are preferred from the perspective of mass production and cost, and coconut shell carbonized products are particularly preferred.
[0101] As a method for carbonizing and activating these raw materials into activated carbon 1, for example, known methods such as a fixed bed method, a moving bed method, a fluidized bed method, a slurry method, and a rotary kiln method can be used. As a carbonization method for these raw materials, an inert gas such as nitrogen, carbon dioxide, helium, argon, xenon, neon, carbon monoxide, and combustion exhaust gas can be cited, or a mixed gas with these inert gases as the main component and other gases can be used to burn at about 400 to 700°C (preferably 450 to 600°C) for about 30 minutes to 10 hours. As an activation method for the carbide obtained by the carbonization method described above, it is preferred to use a gas activation method using an activation gas such as water vapor, carbon dioxide, and oxygen for firing. Among these, as an activation gas, a method using water vapor or carbon dioxide is preferred. In the activation method, it is preferred that the activation gas is supplied at a ratio of 0.5 to 3.0 kg / h (preferably 0.7 to 2.0 kg / h), and the obtained carbide is heated to 800 to 1,000°C for 3 to 12 hours (preferably 5 to 11 hours, and more preferably 6 to 10 hours) for activation. Furthermore, before the activation treatment of the carbide described above, the carbide may be activated once in advance. In this activation, it is generally preferred to use a method of gas activation by firing the carbon material at a temperature below 900°C using an activation gas such as water vapor, carbon dioxide, and oxygen. Activated carbon 1 can be manufactured by appropriately combining the firing temperature and firing time in the carbonization method described above with the activation gas supply amount, heating rate, and maximum activation temperature in the activation method.
[0102] The average particle size of activated carbon 1 is preferably 2 to 20 μm. When the average particle size is 2 μm or more, the capacity per unit volume of the electrode tends to increase due to the high density of the active material layer. It should be noted that if the average particle size is small, it may lead to the disadvantage of low durability, but if the average particle size is 2 μm or more, such a disadvantage is not easy to occur. On the other hand, when the average particle size is 20 μm or less, it tends to be easily suitable for high-speed charge and discharge. The average particle size of activated carbon 1 is more preferably 2 to 15 μm, and further preferably 3 to 10 μm.
[0103] (Activated carbon 2)
[0104] From the perspective of increasing the output characteristics after assembling the positive electrode material into the storage element, the mesopore volume V1 of the activated carbon 2 is preferably greater than 0.8cc / g. From the perspective of suppressing the reduction in the capacity of the storage element, V1 is preferably less than 2.5cc / g. V1 is more preferably 1.00cc / g or more and 2.0cc / g or less, and further preferably 1.2cc / g or more and 1.8cc / g or less. In order to increase the specific surface area of the activated carbon and increase the capacity, the micropore volume V2 of the activated carbon 2 is preferably greater than 0.8cc / g. From the perspective of increasing the density of the activated carbon as an electrode and increasing the capacity per unit volume, V2 is preferably less than 3.0cc / g. V2 is more preferably greater than 1.0cc / g and less than 2.5cc / g, and further preferably 1.5cc / g or more and less than 2.5cc / g. Compared with the existing activated carbon used as a double-layer capacitor or a lithium ion capacitor, the BET specific surface area of the activated carbon 2 having the above-mentioned mesopore volume and micropore volume is high. The specific value of the BET specific surface area of the activated carbon 2 is preferably 2,300 m 2 / g above 4,000m 2 / g or less, more preferably 3,000m 2 / g above 4,000m 2 / g or less, more preferably 3,200m 2 / g above 3,800m 2 / g or less. BET specific surface area is 2,300m 2 / g or more, it is easy to obtain good energy density; BET specific surface area is 4,000m 2 When the content of the binder is 0.1477 W / g or less, it is not necessary to add a large amount of binder to ensure the strength of the electrode, so the performance per unit volume of the electrode is improved.
[0105] Activated carbon 2 can be obtained, for example, using the raw materials and treatment methods described below. As the carbonaceous material used as the raw material of activated carbon 2, there is no particular limitation as long as it is a carbon source commonly used as an activated carbon raw material, for example, plant raw materials such as wood, wood powder, coconut shells; fossil raw materials such as petroleum asphalt, coke; phenol resin, furan resin, vinyl chloride resin, vinyl acetate resin, melamine resin, urea resin, resorcinol resin and other various synthetic resins, etc. Among these raw materials, phenol resin and furan resin are suitable for making activated carbon with a high specific surface area, and are particularly preferred.
[0106] As a method of carbonizing these raw materials, or a heating method during activation treatment, for example, known methods such as a fixed bed method, a moving bed method, a fluidized bed method, a slurry method, and a rotary kiln method can be cited. The atmosphere during heating uses an inert gas such as nitrogen, carbon dioxide, helium, argon, or a gas mixed with these inert gases as the main component and other gases. It is usually a method of firing at a carbonization temperature of about 400 to 700°C for about 0.5 to 10 hours. As a method for activating carbides, there are gas activation methods using activation gases such as water vapor, carbon dioxide, and oxygen for firing; and alkali metal activation methods that are mixed with alkali metal compounds and then heated. In order to produce activated carbon with a high specific surface area, the alkali metal activation method is preferred. In the activation method, carbide and alkali metal compounds such as KOH and NaOH can be mixed in a mass ratio of 1:1 or more (the amount of alkali metal compound is the same as the amount of carbide, or more than the amount thereof), and then heated in an inert gas atmosphere at 600 to 900 ° C for 0.5 to 5 hours, and then washed with acid and water to remove the alkali metal compound, and further dried. In order to increase the amount of micropores without increasing the amount of mesopores, the amount of carbide can be increased and mixed with KOH during activation. In order to increase both the amount of micropores and the amount of mesopores, the amount of KOH can be increased for use. In addition, in order to mainly increase the amount of mesopores, it is preferred to perform water vapor activation after alkali activation treatment. The average particle size of activated carbon 2 is preferably 2 μm or more and 20 μm or less. More preferably, it is 3 μm or more and 10 μm or less.
[0107] (How to use activated carbon)
[0108] Activated carbons 1 and 2 may be one type of activated carbon, or a mixture of two or more types of activated carbons and the mixture as a whole exhibits the above-mentioned characteristic values. Regarding the above-mentioned activated carbons 1 and 2, any one of them may be selected for use, or the two may be mixed for use. The positive electrode active material may also include materials other than activated carbons 1 and 2 (e.g., activated carbon that does not have the specific V1 and / or V2 described above, or materials other than activated carbon (e.g., conductive polymers, etc.)). In the illustrated embodiment, the total content of activated carbons 1 and 2 is preferably 40.0% by mass or more and 70.0% by mass or less, and more preferably 45.0% by mass or more and 65.0% by mass or less. When this value is 40.0% by mass or more, the energy density can be improved. When this value is 70.0% by mass or less, high temperature durability and high voltage durability can be improved.
[0109] (Carbon Nanotubes)
[0110] The positive electrode active material layer contains carbon nanotubes. The carbon nanotubes contained in the positive electrode active material layer may be the same as or different from the carbon nanotubes contained in the negative electrode active material layer. By containing carbon nanotubes in the positive electrode active material layer, it is possible to expect improvements in various properties. As the improved properties, there can be cited the improvement in the decomposition reaction efficiency of alkali metal compounds different from the positive electrode active material, the inhibition of deactivation of alkali metal ions, and the high durability due to the inhibition of deterioration of the binder at high temperatures, the high output due to the reduction of the internal resistance value of the non-aqueous lithium storage element, the improvement of processability due to the increase in the peel strength of the electrode, the inhibition of deterioration due to electrode peeling in the durability test, the inhibition of gas generation during the high temperature durability test, etc.
[0111] As the carbon nanotubes, single-layer carbon nanotubes and multi-layer carbon nanotubes are suitable, and single-layer carbon nanotubes are particularly preferred. The average fiber diameter of the carbon nanotubes is preferably 1 nm or more and less than 20 nm, more preferably 1.5 nm or more and 15 nm or less. When the average fiber diameter is 1 nm or more, the dispersibility of the carbon nanotubes is improved. When the average fiber diameter is less than 20 nm, a non-aqueous alkali metal storage element with higher input-output characteristics can be provided.
[0112] Carbon nanotubes have a bundle structure in which single-layer carbon nanotubes form a bundle (hereinafter also referred to as "bundled single-layer carbon nanotubes"). The fiber length of one single-layer carbon nanotube is about several microns, and in the bundled single-layer carbon nanotubes, it is estimated that a plurality of single-layer carbon nanotubes are connected or twisted and aggregated to form a fiber length of about several microns to tens of microns. The average fiber diameter of the bundled single-layer carbon nanotubes is 5 nm to 20 nm, preferably 6 nm to 17 nm, and more preferably 7 nm to 14 nm. Bundled single-layer carbon nanotubes tend to easily form aggregates such as wire balls, but if the average fiber diameter of the bundled single-layer carbon nanotubes is 5 nm or more, the dispersibility is improved, and a tendency to suppress the formation of aggregates such as wire balls is observed; if it is 20 nm or less, the bonding and electronic conductivity between the active material particles can be improved. Carbon nanotubes can be synthesized by suitable methods such as chemical vapor deposition, arc discharge, and laser evaporation.
[0113] It is preferred that the carbon nanotubes cover the surface of the positive electrode active material in a mesh shape, and it is also preferred that the carbon nanotubes bridge the positive electrode active materials. "Mesh shape" means that a plurality of carbon nanotubes and / or bundled single-layer carbon nanotubes cross each other in various directions on the surface of the active material to form a mesh-like structure consisting of a portion covered by the carbon nanotubes and a portion exposed by the active material.
[0114] When the content of carbon nanotubes in the positive electrode active material layer is set to A (mass %) and the total mass of the positive electrode active material layer is set to 100 mass %, preferably 0.010≤A≤0.200, more preferably 0.015≤A≤0.170, and further preferably 0.020≤A≤0.150. If A is greater than 0.010, the bonding and electronic conductivity between the positive electrode active material particles can be improved, the resistance rise above 80°C can be suppressed, and the decomposition of the electrolyte can be suppressed by promoting the decomposition of the alkali metal compound contained in the positive electrode active material layer, and the pre-doping amount of alkali metal ions in the negative electrode can be increased. If A is less than 0.200, the carbon nanotubes will not excessively cover the positive electrode active material particles, and the amount of SEI (solid electrolyte interface) generated on the carbon nanotubes in the entire positive electrode active material layer can be reduced, thereby reducing the diffusion resistance of ions.
[0115] The content A of carbon nanotubes in the positive electrode active material layer and the content B of carbon nanotubes in the negative electrode active material layer may be the same (A = B), may be less than it (A < B), or may be more than it, but it is preferably more than it (A > B). In the positive electrode of the non-aqueous alkali metal storage element, charge and discharge mainly occur through electrostatic adsorption and desorption of ions. In contrast, in the negative electrode, charge and discharge occur through the Faraday reaction of alkali metal ions. As a result, there is a charge transfer resistance with respect to alkali metal ions in the negative electrode, so the resistance is higher than that of the positive electrode. Therefore, by reducing the resistance of the negative electrode, the non-aqueous alkali metal storage element can be further reduced in resistance. As described above, if the active material particles are overly coated with carbon nanotubes, the resistance increases. Therefore, it is speculated that by making the content B of carbon nanotubes in the negative electrode active material layer less than the content A of carbon nanotubes in the positive electrode active material layer, the resistance balance between the positive electrode and the negative electrode can be optimized, and the resistance of the non-aqueous alkali metal storage element can be reduced.
[0116] The carbon nanotubes are preferably uniformly dispersed on the surface of and between the positive electrode active material particles. By uniformly dispersing the carbon nanotubes on the surface of and between the positive electrode active material particles, the electron conductivity and adhesiveness between the positive electrode active material particles can be improved, and the content of the binder can be reduced. The binder slowly decomposes in a high-temperature environment of 80 °C or higher or in a high-voltage environment of 4.1 V or higher. Therefore, by reducing the content of the binder, high-temperature durability of 80 °C or higher and high-voltage durability of 4.1 V or higher can be imparted.
[0117] As a method for uniformly dispersing carbon nanotubes on the surface of the positive electrode active material, there is the following method: when preparing a carbon nanotube dispersion liquid or when preparing a slurry-like positive electrode coating liquid, a small amount of a compound containing copper atoms is added. By adding a compound containing copper atoms, copper forms a complex with the coordination functional groups such as carboxyl groups and amino groups of the carbon nanotubes, thereby being able to break up the aggregation of the carbon nanotubes and contributing to the solvation of the coating liquid in the dispersion solvent. Through this operation, the carbon nanotubes can be uniformly dispersed on the surface of the positive electrode active material. By uniformly dispersing the carbon nanotubes, the electron conductivity and adhesiveness between the positive electrode active material particles can be improved, the obtained storage element can be made to have a high output, the mixing amount of the binder can be reduced, and the decomposition reaction of alkali metal compounds other than the positive electrode active material can be promoted.
[0118] (Lithium transition metal oxide)
[0119] The positive electrode active material layer preferably further includes a lithium transition metal compound. By including a lithium transition metal oxide, a high capacity of a non-aqueous alkali metal storage element can be achieved. The lithium transition metal oxide includes a transition metal oxide that can absorb and release lithium. There is no particular limitation on the transition metal oxide used as a positive electrode active material. As a transition metal oxide, for example, an oxide containing at least one element selected from the group consisting of cobalt, nickel, manganese, iron, vanadium and chromium can be cited. As a transition metal oxide, specifically, a compound represented by the following formula can be cited, etc.:
[0120] Li x CoO2{where x satisfies 0≤x≤1},
[0121] Li x NiO2{where x satisfies 0≤x≤1},
[0122] Li x Ni y M (1-y) O2{wherein, M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg and Ti, x satisfies 0≤x≤1, and y satisfies 0.05 <y<0.97}、
[0123] Li x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2{where x satisfies 0≤x≤1},
[0124] Li x MnO2{where x satisfies 0≤x≤1},
[0125] α-Li x FeO2{where x satisfies 0≤x≤1},
[0126] Li x VO2{where x satisfies 0≤x≤1},
[0127] Li x CrO2{where x satisfies 0≤x≤1},
[0128] Li x FePO4{where x satisfies 0≤x≤1},
[0129] Li x MnPO4{where x satisfies 0≤x≤1},
[0130] Li z V2(PO4)3{where z satisfies 0≤z≤3},
[0131] Lix Mn2O4 {where x satisfies 0 ≤ x ≤ 1},
[0132] Li x M y Mn (2-y) O4 {where M is at least one element selected from the group consisting of Co, Mn, Al, Fe, Mg, and Ti, x satisfies 0 ≤ x ≤ 1, and y satisfies 0.05 < y < 0.97},
[0133] Li x Ni a Co b Al (1-a-b) O2 {where x satisfies 0 ≤ x ≤ 1, and a and b satisfy 0.02 < a < 0.97 and 0.02 < b < 0.97},
[0134] Li x Ni c Co d Mn (1-c-d) O2 {where x satisfies 0 ≤ x ≤ 1, and c and d satisfy 0.02 < c < 0.97 and 0.02 < d < 0.97}.
[0135] Among these, from the aspects of high capacity, low resistance, cycle characteristics, decomposition of alkali metal compounds, and suppression of shedding of the positive electrode active material during pre-doping, the above-mentioned formula Li x Ni a Co b Al (1-a-b) O2, Li x Ni c Co d Mn (1-c-d) O2, Li x CoO2, Li x Mn2O4, or Li x FePO4, Li x MnPO4 and Li z compounds represented by V2(PO4)3 are preferred.
[0136] If the positive electrode precursor contains an alkali metal compound different from the positive electrode active material, the alkali metal compound becomes a dopant source of the alkali metal during pre-doping and can be pre-doped into the negative electrode. Therefore, even if the transition metal compound does not contain lithium ions in advance (i.e., x=0 or z=0), it can be used as a non-aqueous alkali metal storage element for electrochemical charge and discharge. The content of lithium transition metal oxide in the positive electrode active material layer of the positive electrode precursor is preferably 8.0 mass% or more and 30.0 mass% or less. If the content of lithium transition metal oxide is 8.0 mass% or more, the non-aqueous alkali metal storage element can achieve high capacity. When the content of lithium transition metal oxide is 30.0 mass% or less, the non-aqueous alkali metal storage element can achieve low resistance.
[0137] (Alkali Metal Compounds)
[0138] The positive electrode active material layer of the positive electrode precursor may contain an alkali metal compound other than the positive electrode active material. The alkali metal compound decomposes in the positive electrode precursor to release cations, which are reduced at the negative electrode, thereby enabling the negative electrode to be pre-doped. Preferably, the positive electrode active material layer of the positive electrode precursor contains an alkali metal compound, so that the positive electrode active material layer of the positive electrode obtained after pre-doping also contains an alkali metal compound.
[0139] As such alkali metal compounds, for example, oxides such as M2O, such as M2O, in which M is one or more selected from Li, Na, K, Rb, and Cs; hydroxides such as MOH; halides such as MF and MCl; carboxylates such as RCOOM (where R is H, alkyl, or aryl), and one or more of them can be used. As alkali metal compounds, specifically, for example, lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, lithium oxide, lithium hydroxide, etc. can be cited. As alkali metal compounds, it is suitable to use one or more alkali metal carbonates selected from lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate, and it is more suitable to use lithium carbonate, sodium carbonate, or potassium carbonate. From the aspect of high capacity per unit mass, lithium carbonate is particularly suitable.
[0140] As a positive electrode precursor, it is sufficient to contain at least one alkali metal compound. The positive electrode precursor can replace the above-mentioned alkali metal compound, or together with the above-mentioned alkali metal compound, contain one or more carbonates, oxides, hydroxides, halides and carboxylates selected from alkaline earth metals (the alkaline earth metal is selected from the group consisting of Be, Mg, Ca, Sr and Ba).
[0141] Alkali metal compounds and alkaline earth metal compounds when used are preferably in microparticle form. The average particle size of the alkali metal compound is preferably 0.1 μm or more and 10 μm or less. If the average particle size is 0.1 μm or more, the dispersibility in the positive electrode precursor is excellent. When the average particle size is 10 μm or less, the surface area of the alkali metal compound increases, so the decomposition reaction is carried out efficiently. In addition, the average particle size of the alkali metal compound is preferably smaller than the average particle size of the activated carbon described above. If the average particle size of the alkali metal compound is smaller than the average particle size of the activated carbon, the electron conduction of the positive electrode active material layer increases, which helps to reduce the resistance of the electrode body or the storage element. There is no particular limitation on the method for determining the average particle size of the alkali metal compound in the positive electrode precursor, and it can be calculated based on the SEM image and SEM-EDX image of the positive electrode cross section. Regarding the method for forming the positive electrode cross section, BIB processing can be used to irradiate an Ar beam from the top of the positive electrode and make a smooth cross section along the end of a shielding plate disposed directly above the sample. Various methods can be used for the micronization of alkali metal compounds. For example, a pulverizer such as a ball mill, a bead mill, a ring mill, a jet mill, or a rod mill can be used.
[0142] When the total mass of the positive electrode active material layer is set to 100% by mass, the content of the alkali metal compound contained in the positive electrode active material layer of the positive electrode precursor is preferably 15.0% by mass or more and 45.0% by mass or less. When this value is 15.0% by mass or more, a sufficient amount of alkali metal ions can be pre-doped in the negative electrode to increase the capacity of the non-aqueous alkali metal storage element. When this value is 45.0% by mass or less, the electronic conduction in the positive electrode precursor can be improved, so the alkali metal compound can be efficiently decomposed. For the positive electrode precursor, in addition to the alkali metal compound, the total amount of the alkali metal compound and the alkaline earth metal compound is preferably within the above range. In addition, the content of the alkali metal compound in the pre-doped positive electrode is preferably 0.1% by mass or more and 5.0% by mass or less. If the content of the alkali metal compound in the pre-doped positive electrode is 0.1% by mass or more, the decomposition of the electrolyte in the positive electrode can be suppressed. In addition, if the content is 5.0% by mass or less, the electronic conduction of the positive electrode can be improved, and the output characteristics can be improved. The alkali metal elements and alkaline earth metal elements can be quantitatively determined by ICP-AES, atomic absorption spectrometry, fluorescent X-ray analysis, neutron radiation analysis, ICP-MS, or the like.
[0143] (Compounds containing copper atoms)
[0144] The positive electrode active material layer preferably contains a compound containing copper atoms. Regarding the concentration of the compound containing copper atoms in the positive electrode active material, based on the total mass of the positive electrode active material layer, it is preferably 1 ppm or more and 500 ppm or less, more preferably 2 ppm or more and 450 ppm or less, and further preferably 10 ppm or more and 450 ppm or less. When the concentration of the compound containing copper atoms is 1 ppm or more based on the copper element, the dispersibility of carbon nanotubes can be improved when the positive electrode coating solution is prepared. The mechanism for improving dispersibility is described below. On the other hand, when the concentration of the compound containing copper atoms is 500 ppm or less based on the copper element, the non-aqueous lithium storage element can be made high-voltage by suppressing the decomposition of the solvent.
[0145] The quantification of copper atoms can be calculated based on the copper element by ICP-AES, atomic absorption spectrometry, fluorescent X-ray spectrometry, neutron radiochemical analysis, ICP-MS (inductively coupled plasma mass spectrometry), etc. For example, regarding ICP-MS, the quantification of copper atoms can be performed by the following method.
[0146] For the positive electrode after cleaning with an organic solvent such as DMC, a strong acid such as concentrated nitric acid, concentrated sulfuric acid, aqua regia, etc. is used for acid decomposition, and the resulting solution is diluted with pure water in a manner such that the acid concentration becomes 2% to 3%. In the acid decomposition, the decomposition can also be appropriately heated and / or pressurized. The resulting dilution is analyzed by ICP-MS. During the analysis, it is preferred to add a known amount of an element as an internal standard. For the obtained measurement results, the copper atoms can be quantified based on a calibration curve pre-made using a standard solution for chemical analysis.
[0147] (Other components of positive electrode active material layer)
[0148] In the positive active material layer of the positive electrode precursor in the present disclosure, in addition to the positive active material and carbon nanotubes, other components such as the above-mentioned alkali metal compound, dispersant, conductive filler, binder and pH adjuster may be included as needed. The dispersant, conductive filler and binder in the positive active material layer can be appropriately selected from the materials exemplified above as the dispersant, conductive filler and binder in the negative active material layer. The content of the dispersant and binder in the positive active material layer can be within the above-mentioned range of the content of the dispersant and binder in the negative active material, respectively. Regarding the content of the conductive filler in the positive active material layer of the positive electrode precursor, relative to 100% by mass of the positive active material, it is preferably in the range of 0 to 20% by mass, and more preferably 1 to 15% by mass. From the perspective of high input, it is preferred to mix as much conductive filler as possible. However, if the mixing amount is higher than 20% by mass, the energy density per unit volume of the positive active material layer will be reduced due to the reduction in the content of the positive active material in the positive active material layer, so it is not preferred.
[0149] When water is used as the solvent of the coating liquid for forming the positive electrode active material layer, the coating liquid may become alkaline due to the addition of an alkali metal compound. Therefore, in the coating liquid for forming the positive electrode active material layer, a pH adjuster may be added to the coating liquid as needed. There is no particular limitation on the pH adjuster, for example, hydrogen halides such as hydrogen fluoride, hydrogen chloride, and hydrogen bromide; halogen oxygen-containing acids such as hypochlorous acid, chlorous acid, and chloric acid; carboxylic acids such as formic acid, acetic acid, citric acid, oxalic acid, lactic acid, maleic acid, and fumaric acid; sulfonic acids such as methanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid; acids such as nitric acid, sulfuric acid, phosphoric acid, boric acid, and carbon dioxide, etc. can be used.
[0150] [Positive electrode collector]
[0151] As a material constituting the positive electrode collector, there is no particular restriction as long as it is a material with high electronic conductivity, which does not dissolve in the electrolyte and deteriorate due to reaction with the electrolyte or ions, and is preferably a metal foil. As the positive electrode collector in the non-aqueous alkali metal storage element disclosed in the present invention, aluminum foil is more preferred. The metal foil can be a common metal foil without concave-convex or through-holes, or a metal foil with concave-convex that has been subjected to embossing, chemical etching, electrolytic deposition, sandblasting, etc., or a metal foil with through-holes such as a metal sheet mesh, a punched metal, and an etched foil. From the perspective of the alkali metal doping process described later, non-porous aluminum foil is further preferred, and the surface of the aluminum foil is particularly preferably roughened. Regarding the thickness of the positive electrode collector, there is no particular restriction as long as the shape and strength of the positive electrode can be fully maintained, for example, preferably 1 to 100 μm. An anchor layer of a conductive material such as graphite, flaky graphite, carbon nanotubes, graphene, Ketjen black, acetylene black, and vapor-grown carbon fiber is preferably provided on the surface of the above-mentioned metal foil. By providing the anchor layer, electrical conduction between the positive electrode current collector and the positive electrode active material layer can be improved, and resistance can be reduced. The thickness of the anchor layer is preferably 0.1 μm to 5 μm per single surface of the positive electrode current collector.
[0152] The thickness of the positive electrode active material layer is preferably 10 μm to 200 μm on each single side of the positive electrode collector. The thickness of the positive electrode active material layer is more preferably 20 μm to 150 μm on each single side, and further preferably 30 μm to 100 μm. If the thickness is 10 μm or more, sufficient charge and discharge capacity can be exhibited. On the other hand, if the thickness is 200 μm or less, the ion diffusion resistance in the electrode can be maintained at a low level. Therefore, sufficient output characteristics can be obtained and the volume of the battery cell can be reduced, thereby improving the energy density. It should be noted that the thickness of the positive electrode active material layer in the case where the positive electrode collector has through holes or bumps refers to the average value of the thickness of each single side of the portion of the positive electrode collector that does not have through holes or bumps.
[0153] <Negative electrode>
[0154] The negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on one or both surfaces of the negative electrode current collector.
[0155] [Negative Electrode Active Material Layer]
[0156] The negative electrode active material layer contains a negative electrode active material and carbon nanotubes, and may contain other optional components such as a dispersant, a conductive filler, and a binder as necessary.
[0157] (Negative electrode active material)
[0158] The negative electrode active material can use a material that can absorb and release alkali metal ions. Specifically, carbon materials, titanium oxides, silicon, silicon oxides, silicon alloys, silicon compounds, tin and tin compounds can be exemplified. Based on the total mass of the negative electrode active material layer, the content of the negative electrode active material in the negative electrode active material layer of the negative electrode precursor is preferably 70% by mass or more, more preferably 80% by mass or more. The negative electrode active material is preferably in a granular form.
[0159] The negative electrode active material preferably contains a carbon material. Relative to the total amount of the negative electrode active material, the content of the carbon material is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the carbon material may be 100% by mass, but from the perspective of obtaining the effect of the combination with other materials, it is preferably 95% by mass or less, or 90% by mass or less. The upper and lower limits of the content range of the carbon material may be arbitrarily combined.
[0160] As carbon materials, for example, there can be mentioned difficult-to-graphitize carbon materials; easily-graphitizable carbon materials; carbon black; carbon nanoparticles; activated carbon; artificial graphite; natural graphite; graphitized mesophase carbon microbeads; graphite whiskers; amorphous carbon materials such as polyphenylene-based substances; carbon materials obtained by heat-treating carbon precursors such as petroleum-based asphalt, coal-based asphalt, mesophase carbon microbeads, coke, synthetic resins (such as phenolic resins, etc.); thermal decomposition products of furfuryl alcohol resins or phenolic varnish resins; fullerenes; carbon nanofibers; and composite carbon materials of these.
[0161] Among these, from the aspect of reducing the resistance of negative electrode, preferably heat-treat under the state that the graphite material of more than one selected from artificial graphite, natural graphite, graphitized mesophase carbon microsphere, graphite whisker and high specific surface area graphite etc. and more than one carbonaceous material precursor selected from petroleum asphalt, coal asphalt, mesophase carbon microbead, coke and synthetic resin (such as phenolic resin etc.) coexists, make the composite carbon material that graphite material and carbonaceous material derived from carbonaceous material precursor are compounded.As carbonaceous material precursor, as long as the material that forms carbonaceous material by heat treatment is not particularly limited, particularly preferably petroleum asphalt or coal asphalt.Before being heat-treated, graphite material can be mixed with carbonaceous material precursor at a temperature higher than the fusing point of carbonaceous material precursor. The heat treatment temperature may be any temperature at which the components generated by volatilization or thermal decomposition of the carbonaceous material precursor used become the carbonaceous material, and is preferably 400° C. to 2,500° C., more preferably 500° C. to 2,000° C., and even more preferably 550° C. to 1,500° C. The atmosphere for the heat treatment is not particularly limited, but a non-oxidizing atmosphere is preferred.
[0162] The BET specific surface area of the composite carbon material is preferably 1 m 2 / g above 50m2 / g or less, more preferably 1.5m 2 / g above 40m 2 / g or less, more preferably 2m 2 / g above 25m 2 / g or less. The BET specific surface area of the composite carbon material is 1m 2 When the carbon composite material has a BET specific surface area of 50 m 2 When the content is 1.3477 W / g or less, the charge and discharge efficiency of lithium ions is improved, and the reductive decomposition of the non-aqueous electrolyte during charge and discharge can be suppressed, so that high high-load charge and discharge cycle characteristics can be exhibited.
[0163] The average pore size of the composite carbon material is preferably 1.5 nm to 25 nm, more preferably 2 nm to 22 nm, further preferably 3 nm to 20 nm, and particularly preferably 3.5 nm to 18 nm. When the average pore size of the composite carbon material is 1.5 nm or more, the number of pores larger than the size of the solvated lithium ions in the non-aqueous electrolyte (about 0.9 nm to 1.2 nm) increases, so the diffusion of the solvated lithium ions in the composite carbon material is good, and the non-aqueous alkali metal storage element using it can show high input-output characteristics. On the other hand, when the average pore size of the composite carbon material is 25 nm or less, the packing density of the negative electrode active material layer using it can be fully improved, so that a high energy density can be shown.
[0164] The composite carbon material may be granular, and its average particle size is preferably 1 μm to 10 μm, more preferably 2 μm to 8 μm, and further preferably 3 μm to 6 μm. When the average particle size of the composite carbon material is 1 μm or more, the charge and discharge efficiency of lithium ions can be improved, and thus high high-load charge and discharge cycle characteristics can be exhibited. When the average particle size of the composite carbon material is 10 μm or less, the reaction sites with lithium ions in the non-aqueous electrolyte are increased, and thus high input-output characteristics can be exhibited.
[0165] The mass ratio of the carbonaceous material in the composite carbon material relative to the graphite material is preferably 1 mass % or more and 20 mass % or less, more preferably 1.2 mass % or more and 15 mass % or less, further preferably 1.5 mass % or more and 10 mass % or less, and further preferably 2 mass % or more and 5 mass % or less. When the mass ratio of the carbonaceous material is 1 mass % or more, the reaction sites with the lithium ions in the non-aqueous electrolyte can be fully increased by the carbonaceous material, and the desolvation of the lithium ions can also be easily performed, so that high input-output characteristics can be displayed. When the mass ratio of the carbonaceous material is 20 mass % or less, the solid diffusion of the lithium ions between the carbonaceous material and the graphite material can be well maintained, so that high input-output characteristics can be displayed. In addition, since the charge and discharge efficiency of lithium ions can be improved, high high-load charge and discharge cycle characteristics can be displayed.
[0166] The doping amount of lithium ions per unit mass of the composite carbon material is preferably 50 mAh / g or more and 700 mAh / g or less, more preferably 70 mAh / g or more and 650 mAh / g or less, further preferably 90 mAh / g or more and 600 mAh / g or less, and further preferably 100 mAh / g or more and 550 mAh / g or less. By doping with lithium ions, the negative electrode potential is reduced. Therefore, in the case of combining the negative electrode and the positive electrode of the composite carbon material doped with lithium ions, the voltage of the non-aqueous alkali metal storage element increases, and the utilization capacity of the positive electrode increases. Therefore, the capacity and energy density of the obtained non-aqueous alkali metal storage element increase. When the doping amount of lithium ions per unit mass of the composite carbon material is 50 mAh / g or more, lithium ions can be well doped even at irreversible sites in the composite carbon material that cannot be detached once lithium ions are inserted, so a high energy density can be obtained. The more the doping amount, the lower the negative electrode potential, and the higher the input-output characteristics, energy density and durability. When the doping amount of lithium ions per unit mass of the composite carbon material is 700 mAh / g or less, side effects such as the precipitation of lithium metal are less likely to occur.
[0167] The BET specific surface area of the graphite material used in the composite carbon material is preferably 0.5 m 2 / g above 80m 2 / g or less, more preferably 1m 2 / g above 70m 2 / g or less, more preferably 1.5m 2 / g above 60m 2 When the BET specific surface area of the graphite material used in the composite carbon material is within the above range, the BET specific surface area of the composite carbon material can be adjusted to the above range.
[0168] The graphite material used in the composite carbon material can be granular, and its average particle size is preferably 1 μm to 10 μm, and more preferably 2 μm to 8 μm. When the average particle size of the graphite material used in the composite carbon material is within the range of 1 μm to 10 μm, the average particle size of the composite carbon material can be adjusted to the above range.
[0169] The carbonaceous material precursor used as the raw material of composite carbon material refers to a solid, liquid or organic material soluble in a solvent that can make a carbonaceous material and a graphite material composite by heat treatment. As the carbonaceous material precursor, for example, asphalt, mesophase carbon microbeads, coke and synthetic resins (such as phenolic resins) etc. can be cited. In these carbonaceous material precursors, from the aspect of manufacturing cost, it is preferred to use cheap asphalt. Asphalt can be roughly divided into petroleum-based asphalt and coal-based asphalt. As petroleum-based asphalt, for example, the distillation residue of crude oil, the fluidity contact decomposition residue (clarified oil, etc.), the residual oil derived from thermal cracking, the ethylene tar obtained when naphtha is cracked, etc. can be illustrated.
[0170] (Carbon Nanotubes)
[0171] The negative electrode active material layer contains carbon nanotubes. The carbon nanotubes contained in the negative electrode active material layer may be the same as or different from the carbon nanotubes contained in the positive electrode active material layer. By containing carbon nanotubes in the negative electrode active material layer, it is possible to expect improvements in various properties. As improved properties, there can be cited the inhibition of deactivation of alkali metal ions, high durability due to inhibition of degradation of the binder at high temperatures, high output due to reduction in the internal resistance value of the non-aqueous lithium storage element, improvement in processability due to increased peel strength of the electrode, inhibition of degradation due to electrode peeling in durability tests, and inhibition of gas generation during high-temperature durability tests.
[0172] As the carbon nanotubes, single-layer carbon nanotubes and multi-layer carbon nanotubes are suitable, and single-layer carbon nanotubes are particularly preferred. The average fiber diameter of the carbon nanotubes is preferably 1 nm or more and less than 20 nm, more preferably 1.5 nm or more and 15 nm or less. When the average fiber diameter is 1 nm or more, the dispersibility of the carbon nanotubes is improved. When the average fiber diameter is less than 20 nm, a non-aqueous alkali metal storage element with higher input-output characteristics can be provided.
[0173] Carbon nanotubes have a bundle structure in which single-layer carbon nanotubes form a bundle (hereinafter also referred to as "bundled single-layer carbon nanotubes"). The fiber length of one single-layer carbon nanotube is about several microns, and in the bundled single-layer carbon nanotubes, it is estimated that a plurality of single-layer carbon nanotubes are connected or twisted and aggregated to form a fiber length of about several microns to tens of microns. The average fiber diameter of the bundled single-layer carbon nanotubes is 5 nm to 20 nm, preferably 6 nm to 17 nm, and more preferably 7 nm to 14 nm. Bundled single-layer carbon nanotubes tend to easily form aggregates such as wire balls, but if the average fiber diameter of the bundled single-layer carbon nanotubes is 5 nm or more, the dispersibility is improved, and a tendency to suppress the formation of aggregates such as wire balls is observed; if it is 20 nm or less, the bonding and electronic conductivity between the active material particles can be improved. Carbon nanotubes can be synthesized by suitable methods such as chemical vapor deposition, arc discharge, and laser evaporation.
[0174] It is preferred that the carbon nanotubes cover the surface of the negative electrode active material in a mesh-like manner, and it is also preferred that the carbon nanotubes bridge the negative electrode active materials. "Mesh-like" means that a plurality of carbon nanotubes and / or bundled single-layer carbon nanotubes cross each other in various directions on the surface of the active material, forming a mesh-like structure consisting of a portion covered by the carbon nanotubes and a portion exposed by the active material.
[0175] When the content of carbon nanotubes in the negative electrode active material layer is set to B (mass %) and the total mass of the negative electrode active material layer is set to 100 mass %, preferably 0.003≤B≤0.120, more preferably 0.005≤B≤0.100, and further preferably 0.007≤B≤0.090. If B is greater than 0.003, the binding property and electronic conductivity between the negative electrode active material particles can be improved, and the resistance rise above 80°C can be suppressed. If B is less than 0.120, the carbon nanotubes will not excessively cover the negative electrode active material particles, and the amount of SEI (solid electrolyte interface) generated on the carbon nanotubes in the entire negative electrode active material layer can be reduced, thereby reducing the diffusion resistance of ions and reducing the irreversible capacity derived from the carbon nanotubes, thereby increasing the pre-doping amount of alkali metal ions in the negative electrode.
[0176] The carbon nanotubes are preferably uniformly dispersed on the surface and between the particles of the negative electrode active material. By uniformly dispersing the carbon nanotubes on the surface and between the particles of the negative electrode active material, the electronic conductivity and bonding between the particles of the negative electrode active material can be improved, and the content of the binder can be reduced. The binder slowly decomposes in a high temperature environment of 80°C or above or in a high voltage environment of 4.1V or above, so by reducing the content of the binder, high temperature durability of 80°C or above and high voltage durability of 4.1V or above can be given.
[0177] (Other components of negative electrode active material layer)
[0178] The negative electrode active material layer may contain, in addition to the negative electrode active material and the carbon nanotubes, optional components such as a dispersant, a binder, and a conductive filler as necessary.
[0179] There is no particular limitation on the dispersant, and for example, it is suitable to use one or more selected from carboxymethyl cellulose, polycarboxylic acids, polycarboxylates, polyvinyl pyrrolidone, polyvinyl alcohol, and surfactants. In particular, by using two or more of the above dispersants, it is possible to take into account both the dispersibility of the carbon nanotubes and the stability of the coating solution. The dispersant is particularly preferably, for example, carboxymethyl cellulose and one or more selected from polyvinyl pyrrolidone and polyvinyl alcohol. Relative to 100% by mass of the solid content in the negative electrode active material layer, the content of the dispersion stabilizer is 0.1% by mass or more and 7.0% by mass or less. If the amount of the dispersion stabilizer is 7.0% by mass or less, the entry and exit and diffusion of ions in the negative electrode active material will not be hindered, and high input-output characteristics will be exhibited.
[0180] As the binder, for example, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), fluororubber, polyimide, latex, styrene-butadiene copolymer, acrylic copolymer, etc. can be used. The content of the binder in the negative electrode active material layer is preferably 0 to 20% by mass, more preferably in the range of 0.1 to 15% by mass, relative to 100% by mass of the negative electrode active material.
[0181] In order to make the carbon nanotubes cover the surface of the negative electrode active material and bridge the negative electrode active material particles, the content of the binder in the negative electrode active material layer is preferably 0% by mass. As a result, the diffusivity of the ions in the negative electrode active material layer is improved, so the storage element can achieve high output. On the other hand, in the state where the carbon nanotubes are not broken but agglomerated in the negative electrode active material layer, if the amount of the binder is 0.1% by mass or more, the adhesion between the negative electrode collector and the negative electrode active material layer is fully improved, and the interface resistance between the collector and the active material layer can be reduced. On the other hand, when the amount of the binder is less than 20% by mass, the amount of the binder will not excessively cover the surface of the negative electrode active material, which can promote the diffusion of ions in the pores of the active material.
[0182] The conductive filler is preferably composed of a conductive carbonaceous material having a higher conductivity than the negative electrode active material. As such a conductive filler, for example, it is preferably one or more selected from carbon black, graphite, graphene, etc. and a mixture of these. As carbon black, for example, Ketjen black and acetylene black can be mentioned. As graphite, for example, flaky graphite can be mentioned. As a conductive filler, carbon black is particularly suitable. Relative to 100% by mass of the negative electrode active material, the content of the conductive filler in the negative electrode active material layer is preferably 25% by mass or less, more preferably in the range of 5% by mass or more and 20% by mass or less. From the aspect of high input, the conductive filler is preferably mixed in the negative electrode active material layer, and from the aspect of maintaining the energy density per unit volume of the storage element, the content is preferably controlled to be less than 25% by mass.
[0183] [Negative electrode current collector]
[0184] As the material constituting the negative electrode collector, it is preferred that the material has high electron conductivity and does not dissolve in the electrolyte, deteriorate due to reaction with the electrolyte or ions, etc., for example, it can be a metal foil. There is no particular limitation on such a metal foil, for example, aluminum foil, copper foil, nickel foil, stainless steel foil, etc. can be cited. As the negative electrode collector in the non-aqueous alkali metal storage element disclosed in the present invention, copper foil is preferred when the non-aqueous electrolyte contains lithium ions, and aluminum foil is preferred when an electrolyte composed of sodium ions or potassium ions is used in the non-aqueous electrolyte. The metal foil used as the negative electrode collector can be a common metal foil without concave-convex or through-holes, or a metal foil with concave-convex that has been subjected to embossing, chemical etching, electrolytic deposition, sandblasting, etc., or a metal foil with through-holes such as a metal sheet, a punched metal, and an etched foil. Regarding the thickness of the negative electrode collector, there is no particular limitation as long as the shape and strength of the negative electrode can be fully maintained, for example, 1 to 100 μm.
[0185] The thickness of the negative electrode active material layer is preferably 10 μm to 70 μm on each single side, and more preferably 15 μm to 60 μm. When the thickness is 10 μm or more, a good charge and discharge capacity can be exhibited. On the other hand, when the thickness is 70 μm or less, the volume of the battery cell can be reduced, thereby increasing the energy density. In the case where the negative electrode collector has holes, the thickness of the negative electrode active material layer refers to the average value of the thickness of each single side of the portion of the negative electrode collector that does not have holes.
[0186] <Partition>
[0187] The positive electrode precursor and the negative electrode are stacked or stacked and wound across the separator to form an electrode stack or electrode winding having a positive electrode precursor, a negative electrode and a separator. As a separator, a polyethylene microporous film or a polypropylene microporous film used in a lithium-ion secondary battery, or a cellulose nonwoven paper used in a double-layer capacitor, etc. can be used. A film composed of organic or inorganic particles can be stacked on one or both sides of these separators. In addition, organic or inorganic particles can be contained inside the separator. The thickness of the separator is preferably 5 μm or more and 35 μm or less. By making it 5 μm or more thick, the self-discharge caused by the internal micro-short circuit tends to decrease, so it is preferred. On the other hand, by making it 35 μm or less thick, the output characteristics of the storage element tend to increase, so it is preferred. In addition, the thickness of the film composed of organic or inorganic particles is preferably 1 μm or more and 10 μm or less. By making it 1 μm or more thick, the self-discharge caused by the internal micro-short circuit tends to decrease, so it is preferred. On the other hand, by setting the thickness to 10 μm or less, the output characteristics of the electric storage element tend to be improved, which is preferable.
[0188] <Exterior body>
[0189] As the outer body, a metal can, a laminated film, etc. can be used. As the metal can, an aluminum metal can is preferred. The metal can can be, for example, in a square, round, cylindrical, etc. shape. As the laminated film, a film formed by laminating a metal foil and a resin film is preferred, and a film having a three-layer structure consisting of an outer resin film / metal foil / inner resin film can be exemplified. The outer resin film is used to prevent the metal foil from being damaged due to contact, etc., and resins such as nylon or polyester can be suitably used. The metal foil is used to prevent the penetration of moisture and gas, and foils of copper, aluminum, stainless steel, etc. can be suitably used. In addition, the inner resin film is used to protect the metal foil from being damaged by the electrolyte contained inside, and is also used to perform melt sealing when the outer body is heat-sealed, and polyolefins, acid-modified polyolefins, etc. can be suitably used.
[0190] <Electrolyte>
[0191] The electrolyte is a non-aqueous electrolyte. That is, the electrolyte contains a non-aqueous solvent. In the non-aqueous electrolyte, based on the total amount of the non-aqueous electrolyte, it contains an alkali metal salt of 0.5 mol / L or more. That is, the non-aqueous electrolyte contains an alkali metal salt as an electrolyte. As the non-aqueous solvent contained in the non-aqueous electrolyte, for example, cyclic carbonates represented by ethylene carbonate, propylene carbonate, etc., and chain carbonates represented by dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc. can be cited.
[0192] As an electrolyte salt containing alkali metal ions dissolved in the above-mentioned non-aqueous solvent, for example, M can be set to Li, Na, K, Rb or Cs, and MFSI, MBF4, MPF6, MClO4, LiB(C2O4)2, LiBF2(C2O4), etc. can be used. The non-aqueous electrolyte contains at least one or more alkali metal ions, and can also contain more than two alkali metal salts, and can also contain alkali metal salts and alkaline earth metal salts selected from beryllium salts, magnesium salts, calcium salts, strontium salts, and barium salts. In the case where the non-aqueous electrolyte contains more than two alkali metal salts, the viscosity increase at low temperatures can be suppressed by the presence of cations with different Stokes radii in the non-aqueous electrolyte, so the low-temperature characteristics of the non-aqueous alkali metal storage element are improved. In the case where the non-aqueous electrolyte contains alkaline earth metal ions other than the above-mentioned alkali metal ions, the non-aqueous alkali metal storage element can achieve high capacity.
[0193] There is no particular limitation on the method of making the non-aqueous electrolyte contain the above-mentioned two or more alkali metal salts, or the method of making the non-aqueous electrolyte contain an alkali metal salt and an alkaline earth metal salt. For example, there can be mentioned a method of dissolving an alkali metal salt containing two or more alkali metal ions in the non-aqueous electrolyte in advance, and a method of dissolving an alkali metal salt and an alkaline earth metal salt in the non-aqueous electrolyte in advance. In addition, the following method can also be mentioned: M in the following formula is one or more selected from Na, K, Rb and Cs, and the positive electrode precursor contains a selected
[0194] Carbonates such as M2CO3;
[0195] Oxides such as M2O;
[0196] Hydroxides such as MOH;
[0197] Halides such as MF and MCl;
[0198] RCOOM (wherein R is H, alkyl or aryl) and other carboxylates; and
[0199] Alkaline earth metal carbonates selected from BeCO3, MgCO3, CaCO3, SrCO3 or BaCO3, and alkaline earth metal oxides, alkaline earth metal hydroxides, alkaline earth metal halides and alkaline earth metal carboxylates
[0200] One or more of the above are decomposed by the pre-doping process described later; etc.
[0201] The electrolyte salt concentration in the electrolyte is preferably in the range of 0.5 to 2.0 mol / L. When the electrolyte salt concentration is 0.5 mol / L or more, anions are sufficiently present to maintain the capacity of the non-aqueous alkali metal storage element. On the other hand, when the electrolyte salt concentration is 2.0 mol / L or less, the salt is sufficiently dissolved in the electrolyte, and the electrolyte can maintain appropriate viscosity and conductivity. In the case where the non-aqueous electrolyte contains two or more alkali metal salts, or contains an alkali metal salt and an alkaline earth metal salt, the total value of their salt concentrations is preferably 0.5 mol / L or more, more preferably in the range of 0.5 to 2.0 mol / L.
[0202] The water content contained in the non-aqueous electrolyte is preferably 0 ppm or more and 500 ppm or less. When the water content is 0 ppm or more, the alkali metal compound in the positive electrode precursor can be slightly dissolved, so it can be pre-doped under mild conditions, thereby achieving high capacity and low resistance. When the water content is 500 ppm or less, the high temperature storage characteristics can be improved by suppressing the decomposition of the electrolyte. The water content in the electrolyte can be measured by the above-mentioned Karl Fischer method.
[0203] The non-aqueous electrolyte solution preferably contains a phosphoric acid ester amide represented by the following general formula (1).
[0204] [Chemistry 2]
[0205]
[0206] In the formula, m represents an integer of 1 or 2, R 1 and R 2 Each of R is independently a branched or straight-chain alkyl group having 1 to 6 carbon atoms, or a branched or straight-chain hydrocarbon group having an unsaturated bond. 1 and R 2 may independently have a substituent selected from the group consisting of an alkylthio group and a saturated heterocyclic group, R 1 With R 2 They may also be bonded to each other to form a 5- to 8-membered ring structure. 3 It represents a branched or linear alkyl group having 1 to 6 carbon atoms or a branched or linear fluorine-containing alkyl group having 1 to 6 carbon atoms.
[0207] R 1 and R 2 Each of R is independently a branched or linear alkyl group having preferably 2 to 5 carbon atoms, more preferably 2 to 4 carbon atoms, or a branched or linear hydrocarbon group having an unsaturated bond. 1 and R 2 , for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, and combinations thereof. 3It is preferably a branched or linear alkyl group, or a branched or linear fluorine-containing alkyl group having 1 to 5 carbon atoms, more preferably 1 to 4 carbon atoms, and still more preferably 1 to 3 carbon atoms. 3 Examples of R include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, and groups in which one or more hydrogen atoms in these groups are replaced by fluorine atoms, and combinations thereof. 3 , for example, fluorine-containing methyl, fluorine-containing ethyl, fluorine-containing n-propyl and fluorine-containing isopropyl, and combinations thereof are more preferred, and difluoroethyl, trifluoroethyl and tetrafluoropropyl, and combinations thereof are further preferred.
[0208] By mixing the phosphate amide represented by the general formula (1) into the non-aqueous electrolyte, the decomposition of the electrolyte represented by MPF6 (M is Li, Na, K, Rb or Cs) under a high temperature environment of 80°C or above can be suppressed, and gas generation can be suppressed. In addition, by suppressing the reaction between the alkali metal compound and MPF6 in the alkali metal doping process, the alkali metal doping in the negative electrode can be effectively performed.
[0209] Based on the total mass of the non-aqueous electrolyte, the content of phosphate ester amide in the non-aqueous electrolyte is preferably 0.1 mass % or more and 5.0 mass % or less. It is particularly preferably 0.3 mass % or more and 3.0 mass % or less. When the content of phosphate ester amide is 0.1 mass % or more, gas generation in a high temperature environment of 80° C. or more can be suppressed, and alkali metal doping can be effectively performed. When the content of phosphate ester amide is 5.0 mass % or less, the conductivity of the non-aqueous electrolyte can be improved to achieve low resistance.
[0210] As the phosphoric acid ester amide, bis(2,2-difluoroethyl) N,N-dimethyl phosphate, bis(2,2-difluoroethyl) N,N-diethyl phosphate, bis(2,2-difluoroethyl) N,N-di-n-propyl phosphate, bis(2,2-difluoroethyl) N,N-diisopropyl phosphate, bis(2,2,2-trifluoroethyl) N,N-dimethyl phosphate, bis(2,2,2-trifluoroethyl) N,N-diethyl phosphate, bis(2,2,2-trifluoroethyl) N,N-diethyl phosphate, (2,2,2-trifluoroethyl) N,N-di-n-propylamide, bis(2,2,2-trifluoroethyl) N,N-diisopropylamide, bis(2,2,3,3-tetrafluoropropyl) N,N-dimethylamide, bis(2,2,3,3-tetrafluoropropyl) N,N-diethylamide, bis(2,2,3,3-tetrafluoropropyl) N,N-di-n-propylamide, bis(2,2,3,3-tetrafluoropropyl) N,N-diisopropylamide.
[0211] "Method for producing non-aqueous alkali metal energy storage device"
[0212] [Manufacturing of positive electrode precursor]
[0213] The positive electrode precursor has a positive electrode active material layer on one or both sides of the positive electrode collector. In a representative manner, the positive electrode active material layer is fixed on the positive electrode collector. The positive electrode precursor can be manufactured by known manufacturing techniques for electrodes in lithium ion batteries, double-layer capacitors, etc. For example, the positive electrode active material and the alkali metal compound and any other components used as needed are dispersed or dissolved in water or an organic solvent to prepare a slurry-like coating liquid, which is applied to one or both sides of the positive electrode collector to form a coating film, which is dried to obtain a positive electrode precursor. Further pressing is applied to the obtained positive electrode precursor to adjust the film thickness or bulk density of the positive electrode active material layer. The preparation of the coating liquid for forming the positive electrode active material layer, the coating of the coating liquid on the positive electrode collector, the drying of the coating film, and the pressing can be carried out according to the methods described below.
[0214] As described above, it is preferred that the single-layer carbon nanotubes are uniformly dispersed on the surface and between the particles of the positive electrode active material. As a method for uniformly dispersing the single-layer carbon nanotubes on the surface and between the particles of the positive electrode active material, for example, it can be illustrated as follows: a dispersion of single-layer carbon nanotubes is prepared in advance, and other components such as positive electrode active materials are added to the dispersion for mixing; a specific amount of copper atoms is contained in the coating liquid. The dispersion preferably contains single-layer carbon nanotubes and a solvent, and also contains a dispersant. As solvents, for example, water, NMP, etc. can be cited. Among the dispersants, as a dispersant that can be included in the positive electrode active material layer, it can be appropriately selected from the above-mentioned substances, and it is suitable to use one or more selected from carboxymethyl cellulose, polycarboxylic acid, polycarboxylate, polyvinyl pyrrolidone, polyvinyl alcohol, surfactants, etc. It is particularly preferred to use a dispersant containing carboxymethyl cellulose and containing one or more selected from polyvinyl pyrrolidone and polyvinyl alcohol.
[0215] The dispersion of single-layer carbon nanotubes can be prepared by any method. For example, the following method can be cited: dissolving a dispersant in a solvent, mixing single-layer carbon nanotubes in the obtained solution, and dispersing the single-layer carbon nanotubes by appropriate dispersing means. As the dispersing means, for example, ultrasonic treatment, ball mill, bead mill, jet mill and thin film gyratory high-speed mixer can be cited. By adding other components such as positive electrode active material to the above-mentioned single-layer carbon nanotube dispersion as needed, a coating liquid (hereinafter referred to as "coating liquid") for forming a positive electrode active material layer can be prepared.
[0216] In the positive electrode active material layer formed using such a coating liquid, the single-layer carbon nanotubes are evenly dispersed on the surface of the positive electrode active material and between the particles of the positive electrode active material, and can evenly cover them. This can improve the electronic conductivity and bonding between the particles of the positive electrode active material, so that the content of the binder in the positive electrode active material layer can be reduced. The binder will slowly decompose in a high temperature environment above 80°C, so by reducing the content of the binder, high temperature durability above 80°C can be imparted.
[0217] The preparation method of the coating liquid is not particularly limited, and a dispersion machine such as a homogeneous dispersion machine, a multi-axis dispersion machine, a planetary mixer, a thin film gyratory high-speed mixer, etc. can be appropriately used. In order to obtain a coating liquid with a good dispersion state, the coating liquid is preferably dispersed at a peripheral speed of more than 1m / s and less than 50m / s. If the peripheral speed is more than 1m / s, various materials are well dissolved or dispersed, and thus preferably. If the peripheral speed is less than 50m / s, various materials will not be destroyed by the heat or shear force generated by the dispersion, and reagglomeration can be suppressed, and thus preferably.
[0218] Based on the total mass of the positive electrode coating solution, the mass ratio of the total solid content of the positive electrode coating solution excluding the solvent is W T (mass %) is 35 mass % or more and 50 mass % or less. T The upper limit of W is preferably 50% by mass or less, and more preferably 45% by mass or less. T When the W content is less than 50% by mass, the coating thickness can be controlled to be less than the desired thickness when forming the positive electrode precursor, the resistance of the electrode composite material layer can be reduced, and the basis weight unevenness within the coating surface can be suppressed. Therefore, the decomposition uniformity of the alkali metal compound can be ensured when assembling the non-aqueous hybrid capacitor, and the high-temperature storage characteristics are excellent. T The lower limit of W is preferably 35 mass % or more, more preferably 36 mass % or more. T If the amount of the single-layer carbon nanotubes in the positive electrode coating liquid is 35% or more, an electrode with a high stacking density can be produced. The upper and lower limits of the above WT can be combined arbitrarily. Based on the total mass of the solid components contained in the positive electrode coating liquid, the amount of the single-layer carbon nanotubes contained in the positive electrode coating liquid is preferably 0.010% by mass to 0.200% by mass, more preferably 0.030% by mass to 0.180% by mass, and further preferably 0.050% by mass to 0.160% by mass. If it is within this range, the single-layer carbon nanotubes are well dispersed on the surface of the positive electrode active material, and it is easy to form a bundle structure with an average fiber diameter of 5nm or more and 20nm or less, a mesh structure, and a bridge between positive electrode active materials.
[0219] Regarding the dispersion degree of the coating liquid, the particle size measured by a particle size meter is preferably 0.1 μm or more and 100 μm or less. As the upper limit of the dispersion degree, the particle size measured by a particle size meter is more preferably 80 μm or less, and further preferably 50 μm or less. If the particle size is within this range, the material is not crushed during the preparation of the coating liquid, the nozzle clogging during coating, the generation of coating film stripes, etc. can be suppressed, and the coating can be stably performed.
[0220] The viscosity (ηb) of the coating liquid is preferably 100 mPa·s to 10,000 mPa·s, more preferably 300 mPa·s to 5,000 mPa·s, and further preferably 500 mPa·s to 3,000 mPa·s. If the viscosity (ηb) is 100 mPa·s or more, the dripping of the liquid during the formation of the coating film can be suppressed, and the width and thickness of the coating film can be well controlled. In addition, when the viscosity is 10,000 mPa·s or less, the pressure loss of the coating liquid in the flow path is small when using a coating machine, and the coating can be stably applied, and the coating thickness can be easily controlled.
[0221] The positive electrode coating solution preferably satisfies either one of the following (a) and (b), or both.
[0222] (a) At a shear rate of 10 s -1 More than 1000s -1 In the range below, the viscosity decreases monotonically with increasing shear rate.
[0223] (b) Shear rate 100 s -1 More than 1000s -1 In the following range, the ratio X / Y of the maximum value X (mPa·s) of the viscosity to the minimum value Y (mPa·s) of the viscosity is 1.0 or more and 4.0 or less.
[0224] "Monotonically decreasing" means that the shear rate is 1000s -1 The viscosity under the condition is lower than the shear rate of 10s -1 The viscosity under the conditions and the shear rate is 10s -1 Towards 1000s -1 There is no region of increasing viscosity when the shear rate is increased.
[0225] When any one of the above (a) and (b) is met, the generation of agglomerates due to the deterioration of the dispersibility of the coating liquid can be prevented, and it is not easy to cause clogging of the filter and the piping. In addition, even when the solid content ratio of the coating liquid is increased, the viscosity characteristics of the coating liquid can be stably maintained, so that the generation of stripes during coating or the uneven film thickness of the completed electrode can be suppressed. Furthermore, the internal resistance of the non-aqueous alkali metal storage element can be reduced by improving the dispersibility of the coating liquid. The viscosity curve refers to the curve obtained by measuring at 25°C using MCR102 manufactured by Anton-Paar as a rheometer. In addition, the gap between the rotor of the rheometer and the coating liquid is set to 0.5 (mm) for measurement.
[0226] The TI value (thixotropic index value) of the coating liquid is preferably 1.1 or more, more preferably 1.2 or more, and further preferably 1.5 or more. When the TI value is 1.1 or more, the coating film width and thickness can be well controlled.
[0227] There is no particular limitation on the formation of the coating of the positive electrode active material layer, and a coating machine such as a die coater, a comma coater, a knife coater, or a gravure coater can be appropriately used. The coating can be formed by single-layer coating or multi-layer coating. In the case of multi-layer coating, the coating liquid composition can be adjusted so that the content of the components in each layer of the coating is different. When the coating is applied to the positive electrode collector, multiple strips of coating can be applied, intermittent coating can be applied, or multiple strips of intermittent coating can be applied. In the case of forming the positive electrode active material layer on both sides of the positive electrode collector, coating and drying can be performed on one side of the positive electrode collector, and then coating and drying can be performed successively on the other side, or coating and drying can be performed on both sides of the positive electrode collector at the same time. In addition, in this case, the thickness difference between the positive electrode active material layer on the surface and back of the positive electrode collector is preferably less than 10% of the average thickness of the two. As the mass ratio and the film thickness ratio of the positive electrode active material layer on the front and back surfaces approach 1.0, the charge and discharge load is less concentrated on one side, and thus the high-load charge and discharge cycle characteristics are improved.
[0228] After forming a coating of the positive electrode active material layer on the positive electrode collector, the coating is dried. The coating of the positive electrode precursor is preferably dried by a suitable drying method such as hot air drying, infrared (IR) drying, preferably by far infrared, near infrared or hot air. Regarding the drying of the coating, it can be dried at a single temperature, or the temperature can be changed in multiple stages for drying. It is also possible to dry by combining multiple drying methods. The drying temperature is preferably above 25°C and below 200°C, more preferably above 40°C and below 180°C, and further preferably above 50°C and below 160°C. If the drying temperature is above 25°C, the solvent in the coating can be fully volatilized. On the other hand, if it is below 200°C, it is possible to suppress cracking of the coating due to rapid solvent volatilization or segregation of the binder due to migration, and suppress oxidation of the positive electrode collector or the positive electrode active material layer.
[0229] When the total mass of the positive electrode active material layer is 100% by mass, the water content contained in the dried positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less. When the water content is 0.1% by mass or more, the deterioration of the binder caused by excessive drying can be suppressed and low resistance can be achieved. When the water content is 10% by mass or less, the deactivation of alkali metal ions can be suppressed and high capacity can be achieved. In the case of using N-methyl-2-pyrrolidone (NMP) in the preparation of the coating solution, when the total mass of the positive electrode active material layer is 100%, the content of NMP in the dried positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less. The water content contained in the positive electrode active material layer can be measured by, for example, Karl Fischer titration (JIS 0068 (2001) "Method for Determination of Water Content in Chemical Products"). The amount of NMP contained in the positive electrode active material layer can be quantified as follows: the positive electrode active material layer is immersed in ethanol with a mass 50 to 100 times the mass of the positive electrode active material layer at 25° C. for 24 hours to extract NMP, and then measured by GC / MS and quantified based on a pre-made calibration curve.
[0230] The pressing of the positive electrode active material layer can be appropriately performed using a suitable press such as an oil press, a vacuum press, and a roller press. The film thickness, bulk density, and electrode strength of the positive electrode active material layer can be adjusted by the pressing pressure, the gap between the pressing rollers, and the surface temperature of the pressing portion described later. The pressing pressure is preferably 0.5 kN / cm or more and 20 kN / cm or less, more preferably 1 kN / cm or more and 10 kN / cm or less, and further preferably 2 kN / cm or more and 7 kN / cm or less. When the pressing pressure is 0.5 kN / cm or more, the electrode strength can be fully improved. On the other hand, when the pressing pressure is 20 kN / cm or less, the positive electrode active material layer can be adjusted to the desired film thickness or bulk density without causing deflection and wrinkles in the positive electrode. In the case of using a roller press in the pressing, the gap between the pressing rollers can be set to a suitable value in accordance with the manner in which the positive electrode active material layer reaches the desired thickness and bulk density. The pressing speed can be set to a suitable speed at which the positive electrode does not cause deflection and wrinkles.
[0231] The surface temperature of the pressed portion may be room temperature or may be heated as required. When heated, the lower limit of the surface temperature of the pressed portion is preferably a temperature above the melting point -60°C of the adhesive used, more preferably a temperature above the melting point -45°C of the adhesive, and further preferably a temperature above the melting point -30°C of the adhesive. On the other hand, when heated, the upper limit of the surface temperature of the pressed portion is preferably a temperature below the melting point +50°C of the adhesive used, more preferably a temperature below the melting point +30°C of the adhesive, and further preferably a temperature below the melting point +20°C of the adhesive. For example, when polyvinylidene fluoride (melting point 150°C) is used as a binder, the pressed portion is preferably heated to a temperature of 90°C to 200°C, more preferably 105°C to 180°C, and further preferably 120°C to 170°C. In addition, when a styrene-butadiene copolymer (melting point 100°C) is used in the binder, it is preferred to heat the pressing part to a temperature of 40°C to 150°C, more preferably 55°C to 130°C, and further preferably 70°C to 120°C. The melting point of the binder can be determined from the endothermic peak position of DSC (Differential Scanning Calorimetry). For example, using a differential scanning calorimeter "DSC7" manufactured by Perkin Elmer, 10 mg of a sample resin is placed in a measuring cell, and when the temperature is increased from 30°C to 250°C at a heating rate of 10°C / min in a nitrogen atmosphere, the endothermic peak temperature during the heating process is the melting point.
[0232] Multiple pressings can be performed while changing the pressing pressure, gap, speed, and surface temperature of the pressing portion. In the case of multiple coatings of the positive electrode active material layer, longitudinal cutting is preferably performed before pressing. When the positive electrode is pressed without longitudinal cutting of the positive electrode active material layer coated with multiple strips, excessive stress will be applied to the positive electrode collector portion not coated with the positive electrode active material layer, which may cause wrinkles. The positive electrode active material layer can be longitudinally cut again after pressing.
[0233] The volume resistivity of the electrode composite material layer of the positive electrode precursor is preferably 4.0Ω·cm or less, more preferably 3.9Ω·cm or less, and further preferably 3.8Ω·cm or less. If the volume resistivity of the electrode composite material layer is 4.0Ω·cm or less, the conductivity between the active materials increases, and the internal resistance of the non-aqueous lithium storage element can be reduced. The lower limit of the volume resistivity of the electrode composite material layer of the positive electrode precursor is not particularly limited, and can be 1.0Ω·cm or more.
[0234] The interfacial resistance of the positive electrode precursor is preferably 1.5×10 -1 Ω·cm 2 Below, more preferably 1.4×10 -1 Ω·cm 2 Below, more preferably 1.3×10 -1 Ω·cm 2 If the interface resistance is 1.5×10 -1 Ω·cm 2 The lower limit of the interface resistance of the positive electrode precursor is not particularly limited, and may be 1.0×10 -2 Ω·cm 2 The volume resistivity resistance and interface resistance of the composite material layer of the positive electrode precursor were measured using an electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd.
[0235] [Manufacturing of negative electrode]
[0236] The negative electrode of the non-aqueous alkali metal storage element can be manufactured by the manufacturing technology of the electrode in the known lithium ion battery, double electric layer capacitor, etc. For example, the negative electrode active material and other arbitrary components used as needed can be dispersed or dissolved in water or an organic solvent to prepare a slurry-like coating liquid, which is applied to one or both sides of the negative electrode collector to form a coating film, which is dried to obtain the negative electrode. The obtained negative electrode can also be further pressed to adjust the film thickness or bulk density of the negative electrode active material layer. The preparation of the coating liquid for forming the negative electrode active material layer, the coating of the coating liquid on the negative electrode collector, the drying of the coating film, and the pressing can be carried out according to the above-mentioned method for the manufacture of the positive electrode precursor.
[0237] The volume resistivity of the negative electrode composite material layer is preferably 3.0×10 -2 Ω·cm or less, more preferably 2.7×10 -2 Ω·cm or less, more preferably 2.4×10 -2 Ω·cm or less. If the volume resistivity of the electrode composite material layer is 4.0Ω·cm or less, the conductivity between the active materials increases, and the internal resistance of the non-aqueous lithium storage element can be reduced. The lower limit of the volume resistivity of the negative electrode electrode composite material layer is not particularly limited and can be 1.0×10 -3 Ω·cm or more.
[0238] The interfacial resistance of the negative electrode is preferably 1.5×10 -1 Ω·cm 2 Below, more preferably 1.4×10 -1 Ω·cm 2 Below, more preferably 1.3×10 -1 Ω·cm 2 If the interface resistance is 1.5×10 -1 Ω·cm 2 Below this value, the conductivity of the interface between the active material and the current collector increases, and the internal resistance of the non-aqueous lithium storage element can be reduced. The lower limit of the interface resistance of the negative electrode is not particularly limited, and can be 1.0×10 -4 Ω·cm 2 The volume resistivity resistance and interface resistance of the composite material layer of the negative electrode were measured using an electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd.
[0239] [Assembly process]
[0240] In the assembly process, for example, the positive electrode precursor and the negative electrode cut into a single shape are stacked with a separator to form a laminate, and the positive terminal and the negative terminal are connected to the obtained laminate to make an electrode laminate. Alternatively, the positive electrode precursor and the negative electrode can be stacked and wound with a separator, and the positive terminal and the negative terminal are connected to the obtained winding to make an electrode winding. The shape of the electrode winding can be cylindrical or flat. There is no particular limitation on the method for connecting the positive terminal and the negative terminal, and resistance welding, ultrasonic welding and the like can be used. It is preferred to dry the electrode body (electrode laminate or electrode winding) connected to the terminal to remove the residual solvent. The drying method is not limited, and drying can be performed by vacuum drying or the like. The residual solvent is preferably less than 1.5% by mass relative to the total mass of the positive active material layer or the negative active material layer. If the residual solvent is more than 1.5% by mass, the solvent remains in the system, which deteriorates the self-discharge characteristics, and is therefore not preferred. The dried electrode body is preferably stored in an outer body represented by a metal can or a laminated film in a dry environment with a dew point below -40°C, and sealed with only one opening for injecting a non-aqueous electrolyte. If the dew point is higher than -40°C, moisture will adhere to the electrode body, and water will remain in the system, deteriorating the self-discharge characteristics, which is not preferred. The sealing method of the outer body is not particularly limited, and methods such as heat sealing and pulse sealing can be used.
[0241] [Injection, impregnation, and sealing process]
[0242] After the assembly process, a non-aqueous electrolyte is injected into the electrode body housed in the outer body. After the injection, it is preferably further impregnated to fully impregnate the positive electrode, the negative electrode and the separator with the non-aqueous electrolyte. In a state where at least a portion of the positive electrode, the negative electrode and the separator are not impregnated with the electrolyte, the alkali metal doping is uneven in the alkali metal doping process described later, so the resistance of the obtained non-aqueous alkali metal storage element increases or the durability decreases. There is no particular limitation on the impregnation method, for example, the following method can be used: the electrode body after the injection is placed in a reduced pressure chamber in a state where the outer body is open, a vacuum pump is used to make the chamber a reduced pressure state, and then the pressure is restored to atmospheric pressure; etc. After impregnation, the electrode body in the state where the outer body is open can be sealed while the pressure is reduced, thereby sealing.
[0243] [Alkali metal doping process]
[0244] In the alkali metal doping process, it is preferred to apply a voltage between the positive electrode precursor and the negative electrode, decompose the alkali metal compound preferably contained in the positive electrode precursor to release alkali metal ions, and reduce the alkali metal ions at the negative electrode, thereby pre-doping the alkali metal ions in the negative electrode active material layer. In the alkali metal doping process, gases such as CO2 are generated along with the oxidative decomposition of the alkali metal compound in the positive electrode precursor. Therefore, when applying a voltage, it is preferred to take a means of releasing the generated gas to the outside of the outer body. As such means, for example, there can be cited: a method of applying a voltage in a state where a portion of the outer body is opened; a method of pre-setting a suitable gas release means such as an exhaust valve, a gas permeable membrane, etc. on a portion of the outer body, and applying a voltage in this state; and the like.
[0245] [Aging process]
[0246] After the alkali metal doping step, the electrode body is preferably aged. In the aging step, the solvent in the electrolyte is decomposed at the negative electrode, and a solid polymer film permeable to alkali metal ions is formed on the surface of the negative electrode. There is no particular limitation on the aging method, and for example, a method of reacting the solvent in the electrolyte under a high temperature environment can be used.
[0247] [Exhaust process]
[0248] After the aging process, it is preferred to further exhaust gas to reliably remove the gas remaining in the electrolyte, the positive electrode and the negative electrode. In a state where gas remains in at least a portion of the electrolyte, the positive electrode and the negative electrode, ion conduction is hindered, so the resistance of the resulting non-aqueous alkali metal storage element will increase. There is no particular limitation on the exhaust method, for example, the following method can be used: the electrode body is placed in a decompression chamber with the outer body open, and a vacuum pump is used to make the chamber a decompression state; etc. After exhaust, the outer body can be sealed by sealing the outer body to produce a non-aqueous alkali metal storage element.
[0249] 《Applications of non-aqueous alkali metal energy storage devices》
[0250] The storage module can be made by connecting a plurality of non-aqueous alkali metal storage elements of the present disclosure in series or in parallel. The storage module including the non-aqueous alkali metal storage element of the present disclosure can take into account both high input-output characteristics and safety at high temperatures. Therefore, it can be used in power regeneration auxiliary systems, power load balancing systems, uninterruptible power supply systems, contactless power supply systems, energy harvesting systems, storage systems, solar power generation storage systems, electric power steering systems, emergency power supply systems, hub motor systems, idle stop systems, fast charging systems, smart grid systems, etc. The storage system is suitable for natural power generation such as solar power generation or wind power generation, the power load balancing system is suitable for microgrids, etc., and the uninterruptible power supply system is suitable for factory production equipment, etc. In the contactless power supply system, the non-aqueous alkali metal storage element is suitable for the purpose of balancing and storing voltage changes such as microwave power transmission or electric field resonance; in the energy harvesting system, the non-aqueous alkali metal storage element is suitable for the purpose of using electricity generated by vibration power generation, etc.
[0251] In the power storage system, a plurality of non-aqueous alkali metal storage elements are connected in series or in parallel as a battery stack, or the non-aqueous alkali metal storage element is connected in series or in parallel with a lead battery, a nickel-metal hydride battery, a lithium-ion secondary battery or a fuel cell. In addition, the non-aqueous alkali metal storage element disclosed in the present invention can take into account both high input-output characteristics and safety at high temperatures, and can therefore be installed in vehicles such as electric vehicles, plug-in hybrid vehicles, hybrid vehicles, and electric two-wheeled vehicles. The power regeneration assist system, electric power steering system, emergency power supply system, hub motor system, idle stop system or a combination thereof described above are suitable for installation in vehicles.
[0252] Example
[0253] The embodiments of the present disclosure are described in detail below with reference to Examples and Comparative Examples, but the present disclosure is not limited to the following Examples and Comparative Examples.
[0254] 《Example 1》
[0255] <Production Example of Negative Electrode, Positive Electrode Precursor and Electrolyte>
[0256] [Preparation of Carbon Nanotube Dispersion Liquid]
[0257] 0.400 mass % of commercially available single-walled carbon nanotubes, 0.600 mass % of carboxymethyl cellulose (CMC1) as a dispersant, and 99.000 mass % of distilled water were mixed and dispersed at a peripheral speed of 17 m / s using a thin film gyratory high-speed mixer FILMIX manufactured by PRIMIX to prepare a carbon nanotube dispersion.
[0258] [Manufacturing of Negative Electrode 1-1]
[0259] 94.800% by mass of artificial graphite with an average particle size of 4.5 μm, 3.000% by mass of carbon black, 2.000% by mass of carboxymethyl cellulose (CMC2) as a dispersant, and distilled water were mixed to obtain a mixture with a solid content of 28.0% by mass. The obtained mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes using the autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky to obtain a mixture. A carbon nanotube dispersion was mixed in the above-prepared mixture so that the carbon nanotubes were 0.080% by mass and the CMC1 was 0.120% by mass, and the mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes to prepare a negative electrode coating liquid 1-1. The viscosity (ηb) and TI value of the obtained negative electrode coating liquid 1-1 were measured using an E-type viscometer TVE-35H from Toki Sangyo Co., Ltd. As a result, the viscosity (ηb) was 1,560 mPa·s and the TI value was 3.7. The negative electrode coating liquid 1-1 was applied to one side of an electrolytic copper foil having a thickness of 10 μm using a scraper, and dried for 10 minutes using a hot plate heated to 50°C. Next, a roller press was used to press the foil at a pressure of 5 kN / cm and a surface temperature of 25°C at the pressing part, thereby producing the negative electrode 1-1. The total thickness of the negative electrode 1-1 was measured at any 10 locations using a film thickness meter "Linear Gauge Sensor GS-551" manufactured by Ono Keiki Co., Ltd., and the thickness of the negative electrode active material layer was subtracted from the average value to determine the thickness of the negative electrode active material layer. As a result, the thickness of the negative electrode active material layer of the negative electrode 1-1 was 30 μm. The volume resistivity of the negative electrode composite material layer and the negative electrode interface resistance were calculated using the electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd. As a result, the volume resistivity of the composite material layer of the negative electrode 1-1 was 9.13×10 -3 Ω·cm, interface resistance is 1.44×10 -4 Ω·cm.
[0260] [Analysis of negative electrode]
[0261] Gold was sputtered onto the negative electrode active material layer of negative electrode 1-1 in a vacuum of 10 Pa, thereby coating the surface with a gold film having a thickness of several nm. Then, a SEM image of the surface of the negative electrode active material layer was taken under atmospheric exposure under the following conditions.
[0262] (SEM measurement conditions)
[0263] ·Measurement device: Field emission scanning electron microscope S-4700 manufactured by Hitachi High-Technologies Corporation
[0264] Accelerating voltage: 1kV
[0265] Emission current: 10μA
[0266] ·Measurement magnification: 20,000 times
[0267] Detector: Secondary electron detector
[0268] Electron beam incident angle: 90°
[0269] When photographing, the brightness and contrast were adjusted so that there were no pixels reaching the maximum brightness value in the SEM image and the average brightness value fell within the range of 40% to 60% of the maximum brightness value.
[0270] [Manufacturing of Negative Electrodes 1-2 to 1-12]
[0271] Negative electrodes 1-2 to 1-12 were manufactured in the same manner as in [Manufacturing Example of Negative Electrode 1-1] except that the amounts of the components were adjusted as described in Table 1. The volume resistivity of the composite material layer and the negative electrode interface resistance of negative electrode 1-9 were calculated using an electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd. As a result, the volume resistivity of the composite material layer of negative electrode 1-9 was 3.34×10 -2 Ω·cm, and the interface resistance is 3.84×10 -4 Ω·cm.
[0272] Figure 1 This is a SEM image of negative electrode 1-5 taken at a magnification of 20,000 times. It was confirmed that the single-layer carbon nanotubes (2) formed a bundle structure on the surface of the negative electrode active material (1), covered the surface of the negative electrode active material in a mesh shape, and bridged the active materials with each other (3). The mesh-like coating and bridging based on the bundled single-layer carbon nanotubes were also confirmed in negative electrodes 1-1 to 1-4, 1-6 to 1-8, and 1-10 to 1-12. In negative electrodes 1-1 to 1-8 and 1-10 to 1-12, based on the average value of any carbon nanotube 20, it was confirmed that they all had a bundle structure with an average fiber diameter of 9 nm.
[0273] [Table 1]
[0274] Table 1
[0275]
[0276] [Preparation of positive electrode active material]
[0277] The crushed coconut shell carbide was placed in a small carbonization furnace and carbonized at 500°C for 3 hours under a nitrogen atmosphere to obtain a carbide. The obtained carbide was placed in an activation furnace, and the water vapor heated in a preheating furnace was introduced into the activation furnace at 1 kg / h, and the temperature was raised to 900°C for 8 hours for activation. The activated carbide was taken out and cooled in a nitrogen atmosphere to obtain activated activated carbon. The obtained activated activated carbon was washed with water for 10 hours to remove moisture, dried in an electric dryer maintained at 115°C for 10 hours, and then crushed in a ball mill for 1 hour to obtain activated carbon 1-1. The average particle size of activated carbon 1-1 was measured using a laser diffraction particle size distribution measuring device (SALD-2000J) manufactured by Shimadzu Corporation, and the result was 5.5 μm. In addition, the pore distribution of activated carbon 1-1 was measured using a pore distribution measuring device (AUTOSORB-1AS-1-MP) manufactured by Yuasa Ionics. As a result, the BET specific surface area was 2360 m 2 / g, the mesopore volume (V1) is 0.52cc / g, the micropore volume (V2) is 0.88cc / g, and V1 / V2=0.59.
[0278] [Manufacturing of Positive Electrode Precursor 1-1]
[0279] Activated carbon 1-1: 56.200 mass%, carboxymethyl cellulose (CMC3) 2.000 mass%, lithium carbonate 30.000 mass%, carbon black 5.000 mass%, acrylic latex (LTX) 4.500 mass%, PVP (polyvinyl pyrrolidone) 2.000 mass%, and distilled water with a solid content of 34.1 mass% were mixed, and the mixture was dispersed at a rotation speed of 2000 rpm for 20 minutes using an autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky Co., Ltd. to obtain a mixture. A carbon nanotube dispersion was mixed in the obtained mixture so that the carbon nanotubes were 0.120 mass% and the CMC1 was 0.180 mass%, and the mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes to prepare a positive electrode coating liquid 1-1. The viscosity (ηb) and TI value of the obtained positive electrode coating liquid 1-1 were measured using an E-type viscometer TVE-35H manufactured by Toki Sangyo Co., Ltd. As a result, the viscosity (ηb) was 2,340 mPa·s and the TI value was 5.1. In addition, the dispersion of the obtained positive electrode coating liquid 1-1 was measured using a particle size meter manufactured by Yoshimitsu Seiki. As a result, the particle size was 33μm. The positive electrode coating liquid 1-1 was applied to one side of an aluminum foil having a thickness of 15μm using a scraper, and after drying for 10 minutes on a hot plate heated to 50°C, it was pressed using a roller press at a pressure of 6kN / cm and a surface temperature of 25°C at the pressing part, thereby obtaining a positive electrode precursor 1-1. The total thickness of the obtained positive electrode precursor 1-1 was measured at any 10 locations using a film thickness meter Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd., and the film thickness of the positive electrode active material layer was calculated by subtracting the film thickness of the aluminum foil from the average value. As a result, the film thickness of the positive electrode active material layer of the positive electrode precursor 1-1 was 60μm. The volume resistivity of the positive electrode composite material layer and the positive electrode interface resistance were calculated using the electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd. The results showed that the volume resistivity of the composite material layer of the positive electrode precursor 1-1 was 2.97 Ω·cm and the interface resistance was 2.37×10 -2 Ω·cm.
[0280] [Analysis of positive electrode precursor]
[0281] Gold was sputtered on the positive electrode active material layer of the positive electrode precursor 1-1 in a vacuum of 10 Pa, thereby coating the surface with a gold film having a thickness of several nm. Then, a SEM image of the surface of the positive electrode active material layer was taken under atmospheric exposure under the following conditions.
[0282] (SEM measurement conditions)
[0283] ·Measurement device: Field emission scanning electron microscope S-4700 manufactured by Hitachi High-Technologies Corporation
[0284] Accelerating voltage: 1kV
[0285] Emission current: 10μA
[0286] ·Measurement magnification: 20,000 times
[0287] Detector: Secondary electron detector
[0288] Electron beam incident angle: 90°
[0289] When photographing, the brightness and contrast were adjusted so that there were no pixels reaching the maximum brightness value in the SEM image and the average brightness value fell within the range of 40% to 60% of the maximum brightness value.
[0290] [Production Example of Positive Electrode Precursors 1-2 to 1-14]
[0291] Positive electrode precursors 1-2 to 1-14 were manufactured in the same manner as in [Manufacture of positive electrode precursor 1-1] except that the amounts of each component were adjusted as described in Table 2. The volume resistivity and interface resistance of the composite material layer of positive electrode precursor 1-11 were calculated using the electrode resistance measurement system RM2611 manufactured by Hioki Electric Co., Ltd. As a result, the volume resistivity and interface resistance of the composite material layer of positive electrode precursor 1-11 were 4.29 Ω·cm and 1.41×10- 1 Ω·cm.
[0292] Figure 2 This is an SEM image of the positive electrode precursor 1-9 taken at a magnification of 20,000 times. It was confirmed that the single-layer carbon nanotubes (2) formed a bundle structure on the positive electrode active material (4), covered the surface of the positive electrode active material in a mesh shape, and bridged the active materials with each other (3). In the SEM images of the positive electrode precursors 1-1 to 1-8, 1-10 to 1-11, 1-13 to 1-14 taken at a magnification of 20,000 times, it was also confirmed that the single-layer carbon nanotubes formed a bundle structure on the surface of the positive electrode active material, covered the surface of the positive electrode active material in a mesh shape, and bridged the positive electrode active materials with each other. In the positive electrode precursors 1-1 to 1-11, 1-13 to 1-14, based on the average value of any carbon nanotube 20, it was confirmed that they all had a bundle structure with an average fiber diameter of 9nm.
[0293] [Table 2]
[0294] Table 2
[0295]
[0296] [Preparation of Electrolyte 1-1]
[0297] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 33:67 (volume ratio) was used as an organic solvent, and the electrolyte salt was dissolved in a manner such that the concentration ratio of LiPF6 to LiFSI was 1:1 and the total concentration was 1.2 mol / L to obtain a non-aqueous electrolyte solution 1-1.
[0298] [Preparation of electrolyte solution 1-2]
[0299] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 33:67 (volume ratio) was used as an organic solvent, and the electrolyte salt was dissolved in such a manner that the concentration of bis(2,2,2-trifluoroethyl) N,N-diisopropylamide phosphate was 2.0 mass%, the concentration ratio of LiPF6 to LiFSI was 1:1, and the total concentration was 1.2 mol / L, thereby obtaining a non-aqueous electrolyte 1-2.
[0300] 《Example 1-1》
[0301] <Manufacturing of Non-aqueous Alkali Metal Storage Device>
[0302] [Assembly process]
[0303] The obtained positive electrode precursor 1-1 is cut into a piece according to the size of the positive electrode active material layer of 4.4cm×9.4cm. Then, the negative electrode 1-1 is cut into a piece according to the size of the negative electrode active material layer of 4.5cm×9.5cm. In addition, a 4.7cm×9.8cm polyethylene separator (manufactured by Asahi Kasei, thickness 15μm) is prepared. Using these parts, the positive electrode active material layer and the negative electrode active material layer are stacked opposite to each other with the separator sandwiched therebetween in the order of the positive electrode precursor 1-1, the separator and the negative electrode 1-1 to obtain an electrode laminate. The positive terminal and the negative terminal are ultrasonically welded to the obtained electrode body, and it is loaded into an outer body formed by an aluminum laminate packaging material, and the three sides including the electrode terminal part are sealed by heat sealing.
[0304] [Injection, impregnation, and sealing process]
[0305] Under atmospheric pressure, in a dry air environment with a temperature of 25°C and a dew point of less than -40°C, about 2.5g of non-aqueous electrolyte 1-1 is injected into the outer body containing the electrode laminate. Next, the outer body containing the electrode laminate and the non-aqueous electrolyte is placed in a decompression chamber, and after the pressure is reduced from atmospheric pressure to -87kPa, it is returned to atmospheric pressure and allowed to stand for 5 minutes. Thereafter, after the outer body in the chamber is decompressed from atmospheric pressure to -87kPa, it is returned to atmospheric pressure, and after the process is repeated 4 times, it is allowed to stand at atmospheric pressure for 15 minutes. The non-aqueous electrolyte 1-1 is impregnated into the electrode laminate through the above process. Thereafter, the electrode laminate impregnated with the non-aqueous electrolyte 1-1 is placed in a decompression sealing machine, and sealed at a pressure of 0.1MPa for 10 seconds at 180°C under a state of decompression to -95kPa, thereby sealing the outer body.
[0306] [Alkali metal doping process]
[0307] The sealed electrode laminate was initially charged at 50°C and 50 mA until the voltage reached 4.5 V, and then charged at 4.5 V for 2 hours. Alkaline metal doping was performed in the negative electrode.
[0308] [Aging process]
[0309] The alkali metal-doped electrode laminate was taken out of the drying oven and discharged at a constant current of 50 mA at 25° C. until the voltage reached 2.0 V, and then discharged at a constant current of 2.0 V for 1 hour to adjust the voltage to 2.0 V. The electrode assembly was then stored in a thermostatic chamber at 85° C. for 12 hours.
[0310] [Exhaust process]
[0311] After aging, a portion of the outer body was unsealed in a dry air environment at a temperature of 25°C and a dew point of -40°C, and the electrode laminate was taken out. The taken-out electrode laminate was placed in a decompression chamber, and the pressure was reduced from atmospheric pressure to -80 kPa in 3 minutes using a diaphragm pump, and then it was restored to atmospheric pressure in 3 minutes, and this process was repeated 3 times in total. Thereafter, the electrode laminate was put back into the outer body, and after the pressure was reduced to -90 kPa using a decompression sealer, it was sealed at 200°C with a pressure of 0.1 MPa for 10 seconds to seal the outer body, thereby manufacturing a non-aqueous alkali metal storage element.
[0312] <Evaluation of Non-aqueous Alkali Metal Energy Storage Device>
[0313] [Measurement of internal resistance Ra]
[0314] The internal resistance Ra (mΩ) in Example 1 is a value obtained by the following method. First, the non-aqueous alkali metal storage element is charged with a constant current at a current value of 20C in a thermostatic chamber set at 25°C until it reaches 4.0V, and then a constant voltage charge of 4.0V is applied for a total of 30 minutes. Next, the sampling interval is set to 0.05 seconds, and a constant current discharge is performed at a current value of 20C until 2.0V is obtained, and a discharge curve (time-voltage) is obtained. In this discharge curve, the voltage values at the moments of discharge time 1 second and 2 seconds are extrapolated by a straight line approximation, and when the voltage obtained when the discharge time = 0 seconds is set as Eo, it is calculated in the form of Ra = ΔE / (current value of 20C) according to the voltage drop ΔE = 4.0-Eo, and the obtained value is the internal resistance Ra. The internal resistance Ra of one of the obtained non-aqueous alkali metal storage elements was measured by the above method in a thermostatic chamber set at 25° C. using a charge and discharge device (5 V, 10 A) manufactured by Asuka Electronics Co., Ltd. The result was 80.5 mΩ. These values are shown in Table 3 as the initial internal resistance Ra.
[0315] [Measurement of Pre-doping Amount in Negative Electrode]
[0316] For another element of the obtained non-aqueous alkali metal storage element, the aluminum laminated packaging material was unsealed and the negative electrode was taken out. The obtained negative electrode was used as a working electrode, and a counter electrode was made by pasting a metal lithium foil with a thickness of 50 μm on a copper foil, and a reference electrode was made by pasting a metal lithium with a thickness of 50 μm on a SUS foil, and an electrode body was made together with a polyethylene separator. The obtained electrode body was inserted into an outer body composed of an aluminum laminated packaging material, and it was impregnated with a non-aqueous electrolyte 1-2 to make a three-pole battery cell. For the obtained three-pole battery cell, a charging and discharging device (TOSCAT-3100) manufactured by Toyo Systems Co., Ltd. was used to perform constant current charging at a current value of 7 mA at 25°C until the potential of the working electrode reached 2.5V. Based on the obtained charging capacity (mAh) and the weight (g) of the negative electrode active material layer, the pre-doping amount in the negative electrode was 289 mAh / g.
[0317] [High voltage and high temperature storage test]
[0318] The rate of change of capacity and resistance after high-voltage and high-temperature storage in Example 1 is a value measured by the following method. First, the battery cell corresponding to the non-aqueous alkali metal storage element is charged at a constant current value of 2C in a thermostatic chamber set at 25°C until it reaches 4.2V, followed by a constant voltage discharge with a constant voltage of 4.2V applied for a total of 30 minutes. Then, after being stored in an environment of 85°C for 2 weeks, the internal resistance Rb after high-voltage and high-temperature storage is measured according to the above-mentioned internal resistance measurement method. Rb / Ra is taken as the resistance change rate after high-voltage and high-temperature storage. For another element in the obtained non-aqueous alkali metal storage element, distilled water is used as a solvent, and the volume is measured according to the Archimedean principle. Then, a high-voltage and high-temperature storage test is performed by the above-mentioned method. After the test, the internal resistance Rb was measured, and the result was that Rb was 91.3mΩ. This value is shown in Table 3 as the internal resistance Rb after high-voltage and high-temperature storage. Furthermore, the volume of the battery cell after the test was measured by the above method. Based on the volume change before and after the high-voltage high-temperature storage test, the amount of gas generated during the high-voltage high-temperature storage test was 3.5 cc.
[0319] 《Examples 1-2 to 1-22, Comparative Examples 1-1 to 1-9》
[0320] A nonaqueous alkali metal energy storage device was produced and evaluated in the same manner as in Example 1-1 except that the negative electrode, positive electrode precursor, and nonaqueous electrolyte solution were those listed in Table 1 and Table 2, respectively.
[0321] [Table 3]
[0322] Table 3
[0323]
[0324] By mixing both the positive electrode and the negative electrode with carbon nanotubes, the initial internal resistance Ra and the internal resistance Rb after high voltage and high temperature storage are reduced. On the other hand, if the content of carbon nanotubes is excessively increased, Ra increases. In addition, by making the content A of carbon nanotubes in the positive electrode greater than the content B of carbon nanotubes in the negative electrode, the initial internal resistance Ra is further reduced.
[0325] 《Example 1-23》
[0326] As the non-aqueous electrolyte, non-aqueous electrolyte 1-2 was used, and a non-aqueous alkali metal storage element was prepared under the same conditions as Example 1-1. Ra was measured using the above method, and the result was 83.2mΩ, and the pre-doping amount of the negative electrode was 310mAh. Then, a high-voltage and high-temperature storage test was performed using the above method. After the test, the internal resistance Rb was measured, and the result was 91.6mΩ. In addition, the volume of the battery cell after the test was measured using the above method. According to the volume change before and after the high-voltage and high-temperature storage test, the amount of gas generated in the high-voltage and high-temperature storage test was 1.8cc.
[0327] 《Example 2》
[0328] <Production Example of Negative Electrode, Positive Electrode Precursor and Electrolyte>
[0329] [Preparation of Carbon Nanotube Dispersion Liquid]
[0330] 0.400 mass % of commercially available single-walled carbon nanotubes, 0.600 mass % of carboxymethyl cellulose (CMC1) as a dispersant, and 99.000 mass % of distilled water were mixed and dispersed at a peripheral speed of 17 m / s using a thin film gyratory high-speed mixer FILMIX manufactured by PRIMIX to prepare a carbon nanotube dispersion.
[0331] [Manufacturing of Negative Electrode 2-1]
[0332] 94.800% by mass of artificial graphite with an average particle size of 4.5 μm, 3.000% by mass of carbon black, 2.000% by mass of carboxymethyl cellulose (CMC2) as a dispersant, and distilled water were mixed to obtain a mixture with a solid content of 28.0% by mass. The obtained mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes using the autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky to obtain a mixture. A carbon nanotube dispersion was mixed in the above-prepared mixture so that the carbon nanotubes were 0.080% by mass and the CMC1 was 0.120% by mass, and the mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes to prepare a negative electrode coating liquid 2-1. The viscosity (ηb) and TI value of the obtained negative electrode coating liquid 2-1 were measured using an E-type viscometer TVE-35H from Toki Sangyo Co., Ltd. As a result, the viscosity (ηb) was 1,560 mPa·s and the TI value was 3.7. The negative electrode coating liquid 2-1 was applied to one side of an electrolytic copper foil having a thickness of 10 μm using a scraper, and dried for 10 minutes using a hot plate heated to 50°C. Next, a roller press was used to press the negative electrode 2-1 under the conditions of a pressure of 5 kN / cm and a surface temperature of 25°C at the pressing part. The total thickness of the negative electrode 2-1 was measured at any 10 locations using a film thickness meter "Linear Gauge Sensor GS-551" manufactured by Ono Keiki Co., Ltd., and the thickness of the negative electrode active material layer was calculated by subtracting the thickness of the electrolytic copper foil from the average value. As a result, the thickness of the negative electrode active material layer of the negative electrode 2-1 was 30 μm.
[0333] [Analysis of negative electrode]
[0334] Gold was sputtered onto the negative electrode active material layer of negative electrode 2-1 in a vacuum of 10 Pa, thereby coating the surface with a gold film having a thickness of several nm. Then, a SEM image of the surface of the negative electrode active material layer was taken under atmospheric exposure under the following conditions.
[0335] (SEM measurement conditions)
[0336] ·Measurement device: Field emission scanning electron microscope S-4700 manufactured by Hitachi High-Technologies Corporation
[0337] Accelerating voltage: 1kV
[0338] Emission current: 10μA
[0339] ·Measurement magnification: 20,000 times
[0340] Detector: Secondary electron detector
[0341] Electron beam incident angle: 90°
[0342] When photographing, the brightness and contrast were adjusted so that there were no pixels with the maximum brightness value in the SEM image and the average brightness value fell within the range of 40% to 60% of the maximum brightness value. Figure 1 Similarly, mesh-like coating and bridging by the bundled single-walled carbon nanotubes were confirmed. In the negative electrode 2-1, the average fiber diameter was confirmed to be 9 nm based on the average value of any carbon nanotubes 20.
[0343] [Manufacturing of Negative Electrode 2-2]
[0344] Except adjusting the usage of each component as described in Table 4, the negative electrode 2-2 was produced in the same manner as in [Production Example of Negative Electrode 2-1].
[0345] [Table 4]
[0346] Table 4
[0347]
[0348] [Preparation of positive electrode active material]
[0349] The crushed coconut shell carbide was placed in a small carbonization furnace and carbonized at 500°C for 3 hours under a nitrogen atmosphere to obtain a carbide. The obtained carbide was placed in an activation furnace, and the water vapor heated in a preheating furnace was introduced into the activation furnace at 1 kg / h, and the temperature was raised to 900°C for 8 hours for activation. The activated carbide was taken out and cooled in a nitrogen atmosphere to obtain activated activated carbon. The obtained activated activated carbon was washed with water for 10 hours to remove moisture, dried in an electric dryer maintained at 115°C for 10 hours, and then crushed in a ball mill for 1 hour to obtain activated carbon 2-1. The average particle size of activated carbon 2-1 was measured using a laser diffraction particle size distribution measuring device (SALD-2000J) manufactured by Shimadzu Corporation, and the result was 5.5 μm. In addition, the pore distribution of activated carbon 2-1 was measured using a pore distribution measuring device (AUTOSORB-1AS-1-MP) manufactured by Yuasa Ionics. As a result, the BET specific surface area was 2360 m 2 / g, the mesopore volume (V1) is 0.52cc / g, the micropore volume (V2) is 0.88cc / g, and V1 / V2=0.59.
[0350] [Manufacturing of Positive Electrode Precursor 2-1]
[0351] Activated carbon 2-1: 56.200 mass%, carboxymethyl cellulose (CMC3) 2.000 mass%, lithium carbonate 30.000 mass%, carbon black 5.000 mass%, acrylic latex (LTX) 4.500 mass%, PVP (polyvinyl pyrrolidone) 2.000 mass%, and distilled water with a solid content of 34.1 mass% were mixed, and the mixture was dispersed at a rotation speed of 2000 rpm for 20 minutes using an autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky Co., Ltd. to obtain a mixture. A carbon nanotube dispersion was mixed with the obtained mixture so that the carbon nanotubes were 0.120 mass% and the CMC1 was 0.180 mass%, and the mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes to prepare a positive electrode coating liquid 2-1. The viscosity (ηb) and TI value of the obtained positive electrode coating liquid 2-1 were measured using an E-type viscometer TVE-35H manufactured by Toki Sangyo Co., Ltd. As a result, the viscosity (ηb) was 2,340 mPa·s and the TI value was 5.1. In addition, the dispersion of the obtained positive electrode coating liquid 2-1 was measured using a particle size meter manufactured by Yoshimitsu Seiki. As a result, the particle size was 33μm. The positive electrode coating liquid 2-1 was applied to one side of an aluminum foil with a thickness of 15μm using a scraper, and after drying for 10 minutes on a hot plate heated to 50°C, it was pressed using a roller press at a pressure of 6kN / cm and a surface temperature of 25°C at the pressing part, thereby obtaining a positive electrode precursor 2-1. The total thickness of the obtained positive electrode precursor 2-1 was measured at any 10 locations using a film thickness meter Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd., and the film thickness of the aluminum foil was subtracted from the average value to obtain the film thickness of the positive electrode active material layer. As a result, the film thickness of the positive electrode active material layer of the positive electrode precursor 2-1 was 60μm.
[0352] [Analysis of positive electrode precursor]
[0353] Gold was sputtered on the positive electrode active material layer of the positive electrode precursor 2-1 in a vacuum of 10 Pa, thereby coating the surface with a gold film having a thickness of several nm. Then, a SEM image of the surface of the positive electrode active material layer was taken under atmospheric exposure under the following conditions.
[0354] (SEM measurement conditions)
[0355] ·Measurement device: Field emission scanning electron microscope S-4700 manufactured by Hitachi High-Technologies Corporation
[0356] Accelerating voltage: 1kV
[0357] Emission current: 10μA
[0358] ·Measurement magnification: 20,000 times
[0359] Detector: Secondary electron detector
[0360] Electron beam incident angle: 90°
[0361] When photographing, the brightness and contrast were adjusted so that there were no pixels reaching the maximum brightness value in the SEM image and the average brightness value fell within the range of 40% to 60% of the maximum brightness value.
[0362] [Manufacturing of Positive Electrode Precursor 2-2]
[0363] Except adjusting the usage of each component as described in Table 5, the same procedure as in [Production of Positive Electrode Precursor 2-1] was carried out to produce a positive electrode precursor 2-2.
[0364] The positive electrode precursor 2-1 was photographed at a magnification of 30,000 times, and the obtained SEM image confirmed that the single-layer carbon nanotube formed a bundle structure on the surface of the positive electrode active material, covered the surface of the positive electrode active material in a mesh shape, and bridged the positive electrode active materials. In addition, the average value of any carbon nanotube 20 confirmed that the average fiber diameter was 9nm.
[0365] [Table 5]
[0366] Table 5
[0367]
[0368] [Preparation of Electrolyte 2-1]
[0369] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 33:67 (volume ratio) was used as an organic solvent, 2.0 mass % of bis(2,2,2-trifluoroethyl) N,N-diisopropylamide phosphate as additive 1 was mixed, and the electrolyte salt was dissolved in a manner such that the concentration ratio of LiPF6 to LiFSI was 1:1 and the total concentration was 1.2 mol / L, thereby obtaining a non-aqueous electrolyte 2-1.
[0370] [Preparation of electrolyte 2-11]
[0371] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 33:67 (volume ratio) was used as an organic solvent, and the electrolyte salt was dissolved in such a manner that the concentration ratio of LiPF6 to LiFSI was 1:1 and the total concentration was 1.2 mol / L, thereby obtaining a non-aqueous electrolyte solution 2-11.
[0372] [Preparation of Electrolyte Solutions 2-2 to 2-10 and 2-12 to 2-15]
[0373] Except for adjusting the amount of additive 1 as described in Table 6, non-aqueous electrolyte solutions 2-2 to 2-10 and 2-12 to 2-15 were prepared in the same manner as in [Preparation of electrolyte solution 2-1].
[0374] 《Example 2-1》
[0375] <Manufacturing of Non-aqueous Alkali Metal Storage Device>
[0376] [Assembly process]
[0377] The obtained positive electrode precursor 2-1 is cut into a piece according to the size of the positive electrode active material layer of 4.4cm×9.4cm. Then, the negative electrode 2-1 is cut into a piece according to the size of the negative electrode active material layer of 4.5cm×9.5cm. In addition, a 4.7cm×9.8cm polyethylene separator (manufactured by Asahi Kasei, thickness 15μm) is prepared. Using these parts, the positive electrode active material layer and the negative electrode active material layer are stacked opposite to each other with the separator sandwiched in the order of the positive electrode precursor 2-1, the separator, and the negative electrode 2-1 to obtain an electrode laminate. The positive terminal and the negative terminal are ultrasonically welded to the obtained electrode body, and it is loaded into an outer body formed by an aluminum laminate packaging material, and the three sides including the electrode terminal part are sealed by heat sealing.
[0378] [Injection, impregnation, and sealing process]
[0379] Under atmospheric pressure, in a dry air environment with a temperature of 25°C and a dew point of less than -40°C, about 2.5g of non-aqueous electrolyte 2-1 is injected into the outer body containing the electrode laminate. Next, the outer body containing the electrode laminate and the non-aqueous electrolyte is placed in a decompression chamber, and after the pressure is reduced from atmospheric pressure to -87kPa, it is returned to atmospheric pressure and allowed to stand for 5 minutes. Thereafter, after the outer body in the chamber is decompressed from atmospheric pressure to -87kPa, it is returned to atmospheric pressure, and after the process is repeated 4 times, it is allowed to stand at atmospheric pressure for 15 minutes. The non-aqueous electrolyte 2-1 is impregnated into the electrode laminate through the above process. Thereafter, the electrode laminate impregnated with the non-aqueous electrolyte 2-1 is placed in a decompression sealing machine, and sealed at a pressure of 0.1MPa for 10 seconds at 180°C under a state of decompression to -95kPa, thereby sealing the outer body.
[0380] [Alkali metal doping process]
[0381] The sealed electrode laminate was initially charged at 50°C and 50 mA until the voltage reached 4.5 V, and then charged at 4.5 V for 2 hours. Alkaline metal doping was performed in the negative electrode.
[0382] [Aging process]
[0383] The alkali metal-doped electrode laminate was taken out of the drying oven and discharged at a constant current of 50 mA at 25° C. until the voltage reached 2.0 V, and then discharged at a constant current of 2.0 V for 1 hour to adjust the voltage to 2.0 V. The electrode assembly was then stored in a thermostatic chamber at 85° C. for 12 hours.
[0384] [Exhaust process]
[0385] After aging, a portion of the outer body was unsealed in a dry air environment at a temperature of 25°C and a dew point of -40°C, and the electrode laminate was taken out. The taken-out electrode laminate was placed in a decompression chamber, and the pressure was reduced from atmospheric pressure to -80 kPa in 3 minutes using a diaphragm pump, and then it was restored to atmospheric pressure in 3 minutes, and this process was repeated 3 times in total. Thereafter, the electrode laminate was put back into the outer body, and after the pressure was reduced to -90 kPa using a decompression sealer, it was sealed at 200°C with a pressure of 0.1 MPa for 10 seconds to seal the outer body, thereby manufacturing a non-aqueous alkali metal storage element.
[0386] <Evaluation of Non-aqueous Alkali Metal Energy Storage Device>
[0387] [Measurement of internal resistance Ra]
[0388] The internal resistance Ra (mΩ) in Example 2 is a value obtained by the following method. First, the non-aqueous alkali metal storage element is charged with a constant current at a current value of 20C in a thermostatic chamber set at 25°C until it reaches 4.0V, and then a constant voltage charge of 4.0V is applied for a total of 30 minutes. Next, the sampling interval is set to 0.05 seconds, and a constant current discharge is performed at a current value of 20C until 2.0V is obtained, and a discharge curve (time-voltage) is obtained. In this discharge curve, the voltage values at the discharge time of 1 second and 2 seconds are extrapolated by a straight line approximation, and when the voltage obtained when the discharge time = 0 seconds is set as Eo, it is calculated in the form of Ra = ΔE / (current value of 20C) according to the voltage drop ΔE = 4.0-Eo, and the obtained value is the internal resistance. The internal resistance Ra of one of the obtained non-aqueous alkali metal storage elements was measured by the above method in a thermostatic chamber set at 25° C. using a charge and discharge device (5 V, 10 A) manufactured by Asuka Electronics Co., Ltd. The result was 83.2 mΩ. These values are shown in Table 3 as the initial internal resistance Ra.
[0389] [Measurement of Pre-doping Amount in Negative Electrode]
[0390] For another element of the obtained non-aqueous alkali metal storage element, the aluminum laminated packaging material was unsealed and the negative electrode was taken out. The obtained negative electrode was used as a working electrode, and a counter electrode was made by pasting a metal lithium foil with a thickness of 50 μm on a copper foil, and a reference electrode was made by pasting a metal lithium with a thickness of 50 μm on a SUS foil, and an electrode body was made together with a polyethylene separator. The obtained electrode body was inserted into an outer body composed of an aluminum laminated packaging material, and it was impregnated with a non-aqueous electrolyte 2-11 to make a three-pole battery cell. For the obtained three-pole battery cell, a charging and discharging device (TOSCAT-3100) manufactured by Toyo System Co., Ltd. was used to perform constant current charging at a current value of 7 mA at 25°C until the potential of the working electrode reached 2.5V. Based on the obtained charging capacity (mAh) and the weight (g) of the negative electrode active material layer, the pre-doping amount in the negative electrode was 310 mAh / g.
[0391] [High voltage and high temperature storage test]
[0392] The rate of change of capacity and resistance after high-voltage and high-temperature storage in Example 2 is a value measured by the following method. First, the battery cell corresponding to the non-aqueous alkali metal storage element is charged at a constant current value of 2C in a thermostatic chamber set at 25°C until it reaches 4.2V, followed by a constant voltage discharge with a constant voltage of 4.2V applied for a total of 30 minutes. Then, after being stored in an environment of 85°C for 2 weeks, the internal resistance Rb after high-voltage and high-temperature storage is measured according to the above-mentioned internal resistance measurement method. Rb / Ra is taken as the resistance change rate after high-voltage and high-temperature storage. For another element in the obtained non-aqueous alkali metal storage element, distilled water is used as a solvent, and the volume is measured according to the Archimedean principle. Then, a high-voltage and high-temperature storage test is performed by the above-mentioned method. After the test, the internal resistance Rb was measured, and the result was that Rb was 91.6mΩ. This value is shown in Table 3 as the internal resistance Rb after high-voltage and high-temperature storage. Furthermore, the volume of the battery cell after the test was measured by the above method. Based on the volume change before and after the high-voltage high-temperature storage test, the amount of gas generated during the high-voltage high-temperature storage test was 1.8 cc.
[0393] 《Examples 2-2 to 2-11, Comparative Examples 2-1 to 2-4》
[0394] A nonaqueous alkali metal energy storage device was produced and evaluated in the same manner as in Example 2-1 except that the negative electrode, positive electrode precursor, and nonaqueous electrolyte solution were those listed in Table 6. The evaluation results are shown in Table 6.
[0395] The non-aqueous electrolyte contains a phosphate amide represented by the general formula (1), which can inhibit the reaction between the electrolyte and the alkali metal compound in the alkali metal doping process, so that the alkali metal doping reaction in the negative electrode is effectively carried out, and the pre-doping amount of the negative electrode is increased. In addition, the gas generation in a high temperature and high voltage environment such as 80°C and 4.2V is suppressed. Furthermore, by mixing carbon nanotubes in both the positive and negative electrodes, the initial internal resistance Ra and the internal resistance Rb after high voltage and high temperature storage are reduced.
[0396] 《Examples 2-12 to 2-16》
[0397] Additives 2 to 5 shown in Table 6 were further added to the non-aqueous electrolyte 2-1 to prepare non-aqueous electrolytes 2-16 to 2-22. Non-aqueous alkali metal storage devices were prepared under the same conditions as in Example 2-1 except that non-aqueous electrolytes 2-16 to 2-22 were used. The evaluation results are shown in Table 6.
[0398] [Table 6]
[0399] Table 6
[0400]
[0401] Additive 1: Bis(2,2,2-trifluoroethyl) N,N-diisopropylamide phosphate
[0402] Additive 2: LiPO2F2
[0403] Additive 3: 2-amino-1,1,3-tricyano-1-propene
[0404] Additive 4: 1-Butyl-3-methylimidazolium tricyanomethane
[0405] Additive 5: Lithium tricyanomethanide
[0406] 《Example 3》
[0407] The effect of containing carbon nanotubes and a specific amount of a compound containing a copper element in the positive electrode active material layer of the positive electrode precursor (and the positive electrode) was verified in the following Example 3. The example in which the positive electrode active material layer contains carbon nanotubes and a specific amount of a compound containing a copper element is recorded as an "Example", and the example not containing these components is recorded as a "Comparative Example".
[0408] [Doping efficiency]
[0409] In Example 3, the doping efficiency η (%) is a value obtained by the following method.
[0410] The positive electrode monopolar battery cell was heated in a thermostatic chamber set at 45°C with a current value of 0.49 mA / cm per unit electrode area of the positive electrode. 2Alkali metal doping is performed by performing constant current charging until the voltage reaches 4.5V, and then continuing to perform constant voltage charging at 4.5V for 3 hours. At this time, when the capacity increase of the battery cell voltage above 4.3V is set to Q (mAh), the mass of the alkali metal compound contained in the positive electrode active material layer is set to M (g), and the theoretical capacity of the alkali metal compound is set to B (mAh / g), the doping efficiency η (%) is calculated by η = Q / (M×B)×100. B is obtained by dividing the product of the Faraday constant (96500C / mol=26.8Ah / mol) and the amount of alkali metal contained in the chemical formula (for example, 2 in the case of Li2CO3 and 3 in the case of Li3PO4) by the molecular weight of the compound.
[0411] [Negative electrode potential]
[0412] In Example 3, the negative electrode potential Vp (mV) is a value obtained by the following method.
[0413] The battery cell corresponding to the non-aqueous lithium storage element was discharged at a constant current value of 2C in a thermostatic chamber set at 25°C until it reached 2.2 V, and then discharged at a constant voltage of 2.2 V for 20 minutes. Thereafter, the potential relative to the metal lithium reference electrode was measured and taken as the negative electrode potential (mV).
[0414] [Capacitance]
[0415] In Example 3, the capacity Qa (mAh) is a value obtained by the following method.
[0416] First, the battery cell corresponding to the non-aqueous lithium storage element was charged at a constant current value of 2C in a thermostatic chamber set at 25°C until it reached 4.0V, and then constant voltage charging was performed for a total of 30 minutes with a constant voltage of 4.0V. Thereafter, constant current discharge was performed at a current value of 2C until it reached 2.0V, and the capacity at this time was referred to as Qa (mAh).
[0417] Here, the discharge rate of current (also referred to as "C rate") refers to the relative ratio of the current during discharge to the discharge capacity, and the current value that completes the discharge in 1 hour when performing constant current discharge from the upper limit voltage to the lower limit voltage is generally referred to as 1C. In this specification, the current value that completes the discharge in 1 hour when performing constant current discharge from the upper limit voltage of 4.0V to the lower limit voltage of 2.0V is referred to as 1C.
[0418] [Internal resistance]
[0419] In Example 3, the internal resistance Ra (mΩ) is a value obtained by the following method.
[0420] First, the non-aqueous lithium metal storage element is charged with a constant current of 20C in a thermostatic chamber set at 25°C until it reaches 4.0V, and then a constant voltage charge of 4.0V is applied for a total of 30 minutes. Next, the sampling interval is set to 0.05 seconds, and a constant current discharge is performed at a current value of 20C until 2.0V is obtained to obtain a discharge curve (time-voltage). In this discharge curve, the voltage values at the moments of discharge time 1 second and 2 seconds are extrapolated by a straight line approximation, and when the voltage at the obtained discharge time = 0 seconds is set as Eo, it is calculated in the form of Ra = ΔE / (current value of 20C) according to the voltage drop ΔE = 4.0-Eo, and the obtained value is the internal resistance.
[0421] [Self-discharge coefficient]
[0422] In Example 3, the self-discharge coefficient A (V / h 1 / 2 ) is a value obtained by the following method.
[0423] First, the battery cell corresponding to the non-aqueous lithium storage element was charged with a constant current of 2C in a thermostatic chamber set at 25°C until it reached 4.0V, and then a constant voltage discharge was performed with a constant voltage of 4.0V applied for 30 minutes. The charging completion time at this time was used as the start time of the self-discharge coefficient measurement. The battery cell was then installed to a temperature of 1.0kgf / cm 2 The clamp with a pressure of 100°C is stored in a thermostatic chamber set at 25°C for Ta (h). After storage, the battery cell voltage of the clamp is measured while it is installed in the clamp, and the value at this time is taken as Va. A = (4.0-Va) / (Ta) 1 / 2 Calculate the self-discharge coefficient A (V / h 1 / 2 ). In this specification, Ta=96(h), that is, the self-discharge coefficient is calculated by storing the battery cell under pressure for 4 days.
[0424] [High voltage and high temperature storage test]
[0425] In Example 3, the capacity retention rate (%) and the resistance change rate (%) after high-voltage and high-temperature storage were measured by the following methods.
[0426] First, the battery cell corresponding to the non-aqueous lithium storage element is charged with a constant current of 2C in a thermostatic chamber set at 25°C until it reaches 4.0V, followed by a constant voltage discharge of 4.0V for a total of 30 minutes. Then, after being stored at 80°C for 1 week, the electrostatic capacity Qb and internal resistance Rb after high-voltage and high-temperature storage are measured according to the above-mentioned electrostatic capacity and internal resistance measurement methods. Qb / Qa×100 is taken as the capacity retention rate (%) after high-voltage and high-temperature storage, and Rb / Ra×100 is taken as the resistance change rate (%) after high-voltage and high-temperature storage.
[0427] [High temperature floating test]
[0428] In Example 3, the amount of gas generated V (cc) in the high-temperature floating test was measured by the following method.
[0429] First, the volume of the battery cell before the floating test was calculated from the buoyancy applied to the battery cell in a room temperature solvent (Archimedes method). The volume of the battery cell at this time was defined as V a (cc). Next, the battery cell corresponding to the non-aqueous lithium storage element was charged at a constant current of 2C in a thermostatic chamber set at 80°C until it reached 3.6V, and then a constant voltage discharge of 3.6V was applied for a total of 2 weeks. The volume of the battery cell at room temperature after the test was then calculated using the Archimedean method described above. The volume of the battery cell at this time was taken as V b (cc), V=V b -V a The gas generation amount V (cc) of the high temperature floating test was determined.
[0430] [Preparation of positive electrode active material]
[0431] The following activated carbon was used. The average particle size was measured using a laser diffraction particle size distribution analyzer (SALD-2000J) manufactured by Shimadzu Corporation.
[0432] (1) Coconut shell and steam activated activated carbon 3-1 with a particle size of 4.8 μm were used as raw materials.
[0433] (2) As raw materials, charcoal and activated carbon 3-2 with a particle size of 6.1 μm activated by water vapor were used.
[0434] [Preparation of Carbon Nanotube Dispersion]
[0435] 6.0 mass % of commercially available multilayer carbon nanotubes (CNT) (average fiber diameter 15 nm, average fiber length 5 μm), 1.0 mass % of carboxymethyl cellulose (CMC) as a dispersant, and 91.0 mass % of distilled water were mixed and dispersed at a speed of 100 rpm for 120 minutes using a planetary ball mill to prepare a carbon nanotube dispersion.
[0436] [Manufacturing of Positive Electrode Precursor 3-1]
[0437] Activated carbon 3-1: 54.7 mass % as a positive electrode active material, lithium carbonate 38.1 mass % as an alkali metal compound, carboxymethyl cellulose 1.44 mass % as a dispersant 1, PVP (polyvinyl pyrrolidone) 1.70 mass % as a dispersant 2, and acrylic latex (LTX) 3.96 mass % as a binder, anhydrous copper sulfate equivalent to 10 ppm in terms of copper atomic weight as a copper compound, and the above-mentioned carbon nanotube dispersion in an amount equivalent to 0.099 mass % of the carbon nanotube amount were added, and distilled water was further mixed so that the mass ratio of the solid content was 29.0%. The mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes using an auto-rotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky Co., Ltd. to obtain a positive electrode coating liquid 3-1.
[0438] The positive electrode coating liquid 3-1 was applied to one side of an aluminum foil having a thickness of 15 μm using a doctor blade, dried on a hot plate heated to 50° C. for 10 minutes, and then pressed using a roller press at a pressure of 6 kN / cm and a surface temperature of 25° C. to obtain a positive electrode precursor 3-1.
[0439] The total thickness of the obtained positive electrode precursor 3-1 was measured at 10 random locations using a film thickness meter Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd., and the thickness of the positive electrode active material layer was determined by subtracting the thickness of the aluminum foil from the average value. The thickness of the positive electrode active material layer of the positive electrode precursor 3-1 was 72 μm.
[0440] [Manufacturing of positive electrode precursors 3-2 to 3-20]
[0441] Positive electrode precursors 3-2 to 20 were produced in the same manner as in [Production of Positive Electrode Precursor 3-1] except that the types and amounts of the components were as shown in Table 7 below.
[0442] [Table 7]
[0443] Table 7
[0444]
[0445] [Manufacturing Example of Negative Electrode]
[0446] 82.8% by mass of artificial graphite, 4.3% by mass of porous carbon, 8.7% by mass of acetylene black, 2.0% by mass of CMC (carboxymethyl cellulose), 2.2% by mass of SBR (styrene-butadiene rubber) latex, and distilled water with a solid content of 34.0% by mass are mixed to obtain a mixture thereof. The obtained mixture is dispersed at a rotation speed of 2,000 rpm for 10 minutes using an autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky to obtain a negative electrode coating liquid 3-1. The negative electrode coating liquid 3-1 is applied to one side of an electrolytic copper foil having a thickness of 8 μm using a scraper and dried for 10 minutes on a hot plate heated to 50°C. Next, a roller press is used to press at a pressure of 5 kN / cm and a surface temperature of 25°C at the pressing portion to produce a negative electrode 3-1. The total thickness of the negative electrode 3-1 was measured at 10 random locations using a film thickness meter "Linear Gauge Sensor GS-551" manufactured by Ono Keiki Co., Ltd., and the thickness of the negative electrode active material layer was subtracted from the average value to determine the thickness of the negative electrode active material layer. The thickness of the negative electrode 3-1 was 30 μm.
[0447] [Example of Preparation of Electrolyte Solution]
[0448] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl methyl carbonate (DMC) = 34:22:44 (volume ratio) was used as an organic solvent, and the electrolyte salt was dissolved in a manner such that the concentration ratio of LiPF6 to LiFSI was 3:1 and the total concentration was 1.2 mol / L to obtain a non-aqueous electrolyte solution 3-1.
[0449] [Fabrication of Metal Lithium Counter Electrode]
[0450] Cut the copper foil into 4.6cm×9.6cm(44cm 2 ) and a metal lithium foil cut into a rectangular shape is stacked on it. The lithium foil is then pressed onto the copper foil using a hand roller to obtain a metal lithium counter electrode.
[0451] 《Example 3-1》
[0452] <Manufacturing of Non-aqueous Alkali Metal Storage Device>
[0453] [Fabrication of positive electrode monopolar battery cell]
[0454] The obtained positive electrode precursor 3-1 was made into a 4.3 cm×9.5 cm (41 cm 2 ) size. Also, prepare 4.8cm×9.8cm(47cm 2) polyolefin separator (manufactured by Asahi Kasei Corporation, thickness 15 μm) and 4.8 cm × 9.8 cm (47 cm 2 ) glass filter. Then, the positive electrode precursor 3-1, the separator, the glass filter, and the metal lithium counter electrode are stacked in this order to obtain an electrode laminate. The positive terminal and the negative terminal are ultrasonically welded to the obtained electrode laminate, which is then placed in a container formed of an aluminum laminate packaging material, and the three sides including the electrode terminal portion are sealed by hot air. The electrode laminate thus produced is used as the positive electrode monopolar battery unit 3-1.
[0455] [Assembly]
[0456] Cut the positive electrode precursor 3-1 into a piece of 4.4cm×9.4cm in size with the positive electrode active material layer. Then cut the negative electrode 3-1 into a piece of 4.5cm×9.5cm in size with the negative electrode active material layer. Also prepare a 4.7cm×9.8cm polyethylene separator (manufactured by Asahi Kasei, thickness 15μm). Using these parts, stack the positive electrode active material layer and the negative electrode active material layer opposite to each other with the separator sandwiched in the order of the positive electrode precursor 3-1, the separator, and the negative electrode 3-1 to obtain an electrode laminate. Ultrasonic weld the positive terminal and the negative terminal on the obtained electrode body, load it into an outer body formed by an aluminum laminate packaging material, and seal the three sides including the electrode terminal part by heat sealing. The electrode laminate thus prepared is used as a non-aqueous lithium storage element 3-1.
[0457] [Injection]
[0458] Under atmospheric pressure, in a dry air environment with a temperature of 25°C and a dew point below -40°C, inject about 3.0g of non-aqueous electrolyte 3-1 into the outer casing containing the positive single-pole battery cell 3-1 and the non-aqueous lithium storage element 3-1 manufactured as described above. Next, place the outer casing containing the electrode laminate and the non-aqueous electrolyte in a decompression chamber, decompress the pressure from atmospheric pressure to -87kPa, return to atmospheric pressure, and let it stand for 5 minutes. Thereafter, after decompressing the outer casing in the chamber from atmospheric pressure to -87kPa, return to atmospheric pressure, repeat the process 4 times, and let it stand for 15 minutes at atmospheric pressure. The non-aqueous electrolyte 3-1 is impregnated into the electrode laminate through the above process. Thereafter, the electrode laminate impregnated with the non-aqueous electrolyte solution 3-1 was placed in a vacuum sealer and sealed at a pressure of 0.1 MPa at 180° C. for 10 seconds under a reduced pressure of −95 kPa, thereby hermetically sealing the outer body.
[0459] [Alkali metal doping process]
[0460] Next, the nonaqueous lithium storage element 3-1 was placed in a thermostatic chamber set at 45°C. A charge-discharge device manufactured by Asuka Electronics Co., Ltd. was used to charge and discharge the positive electrode at a current value of 1.2 mA / cm per electrode area. 2 The constant current charge was performed until the voltage reached 4.5 V, and then the constant voltage charge at 4.5 V was continued for 3 hours. The initial charge was performed by this method and the alkali metal doping was performed. Thereafter, the charge-discharge cycle consisting of the following discharge step and charge step was repeated 5 times. In the discharge step, the current value per electrode area of the positive electrode was 1.2 mA / cm 2 The battery was discharged from 4.0V to 2.0V and then discharged at 2.0V for 10 minutes. During this charging process, the current value per electrode area of the positive electrode was 1.2mA / cm 2 The battery was charged from 2.0V to 4.0V with constant current and then continued to charge at 4.0V for 10 minutes.
[0461] [Aging process]
[0462] The nonaqueous lithium storage element 3-1 after the alkali metal doping step was placed in a thermostatic chamber set at 60°C and the current value per electrode area of the positive electrode was 1.2 mA / cm 2 After constant current charging to 4.0 V, constant voltage charging at 4.0 V was performed for 16 hours.
[0463] [Exhaust process]
[0464] For the non-aqueous lithium storage element 3-1 after the aging process, a portion of the aluminum laminated packaging material is unsealed under an argon environment with a temperature of 25°C and a dew point of -60°C. Next, a partially opened aluminum laminated packaging material containing an electrode stack is placed in a decompression chamber, and a diaphragm pump is used to reduce the pressure from atmospheric pressure to -80kPa in 3 minutes, and then restored to atmospheric pressure in 3 minutes, and the process is repeated a total of 10 times. Thereafter, the partially opened aluminum laminated packaging material containing the electrode stack is placed in a decompression sealer, and after the pressure is reduced to -90kPa, it is sealed at 200°C with a pressure of 0.1MPa for 10 seconds, thereby sealing the aluminum laminated packaging material to make a non-aqueous lithium storage element.
[0465] <Evaluation of non-aqueous lithium storage element>
[0466] [Measurement of electrostatic capacitance Qa and internal resistance Ra]
[0467] For the obtained non-aqueous lithium storage element 3-1, the negative electrode potential Vp, electrostatic capacitance Qa and internal resistance Ra were measured by the above method in a constant temperature chamber set at 25°C using a charge and discharge device (5V, 10A) manufactured by Asuka Electronics Co., Ltd. The results were Vp: 133mV, Qa: 7.30mAh, and Ra: 131mΩ.
[0468] [High voltage and high temperature storage test]
[0469] The obtained non-aqueous lithium storage element 3-1 was subjected to a high voltage and high temperature storage test by the above method. After the test, the electrostatic capacitance Qb and the internal resistance Rb were measured, and the results showed that Qb was 4.91 mAh and Rb was 165 mΩ. In addition, the electrostatic capacitance retention rate and the change rate of the internal resistance before and after the high voltage and high temperature storage test were calculated as indicators of high voltage and high temperature storage resistance. The results showed that the capacity retention rate Qb / Qa×100 was 70.9 (%) and the resistance change rate Rb / Ra×100 was 1.28 (%), both of which were good.
[0470] 《Examples 3-2 to 3-11, Comparative Examples 3-1 to 3-9》
[0471] A positive electrode monopolar battery cell was prepared using the positive electrode precursors 3-2 to 3-20 described in Table 7, the metallic lithium described in Example 3-1, and the non-aqueous electrolyte 3-1. In addition, a non-aqueous lithium storage element was prepared using the negative electrode 3-1 described in Example 3-1 and the non-aqueous electrolyte 3-1. In Examples 3-2 to 3-10 and Comparative Examples 3-1 to 3-8, a doping efficiency evaluation based on the positive electrode monopolar battery cell was performed, and after the initial characteristics of the non-aqueous lithium storage element were confirmed, the capacity retention rate and resistance change rate of the high-temperature storage test were measured. In Example 3-11 and Comparative Example 3-9, a doping efficiency evaluation based on the positive electrode monopolar battery cell was performed, and after the initial characteristics of the non-aqueous lithium storage element were confirmed, a high-temperature floating test was performed to measure the gas generation. The evaluation results are listed in Table 8 below.
[0472] [Table 8]
[0473] Table 8
[0474]
[0475] 《Example 4》
[0476] [Internal resistance]
[0477] In Example 4, the internal resistance Ra (mΩ) is a value obtained by the following method. First, the non-aqueous lithium metal storage element is charged with a constant current at a current value of 20C in a thermostatic chamber set at 25°C until it reaches 4.0V, followed by a constant voltage charge of 4.0V for a total of 30 minutes. Next, the sampling interval is set to 0.05 seconds, and a constant current discharge is performed at a current value of 20C until 2.0V is obtained to obtain a discharge curve (time-voltage). In this discharge curve, the voltage values at the discharge times of 1 second and 2 seconds are extrapolated by a straight line approximation, and the voltage obtained when the discharge time = 0 seconds is set as Eo, and the internal resistance is calculated based on the voltage drop ΔE = 4.0-Eo with Ra = ΔE / (current value of 20C), and the obtained value is the internal resistance.
[0478] [Preparation of positive electrode active material]
[0479] The following activated carbon was used. The average particle size was measured using a laser diffraction particle size distribution analyzer (SALD-2000J) manufactured by Shimadzu Corporation.
[0480] (1) Coconut shell and steam activated activated carbon 4-1 with a particle size of 5.3 μm were used as raw materials.
[0481] (2) As raw materials, charcoal and activated carbon 4-2 with a particle size of 6.1 μm activated by water vapor were used.
[0482] (3) Coconut shell and steam activated activated carbon with a particle size of 4.8 μm were used as raw materials.
[0483] [Preparation of Carboxymethyl Cellulose (CMC) Aqueous Solution 4-1]
[0484] 1.5 mass % of commercially available carboxymethyl cellulose and 98.5 mass % of distilled water were mixed and stirred at a rotation speed of 500 rpm for 60 minutes using a homodispersor to prepare a CMC aqueous solution 4-1. The CMC aqueous solution 4-1 was measured using a TVE-35H E-type viscometer from Toki Sangyo Co., Ltd. at a shear rate of 1,000 s -1 The viscosity under the conditions of 1,000 ℃ and 1,000 ℃ was measured. As a result, the viscosity (ηb) was 1,962 mPa·s and the TI value was 2.4.
[0485] [Preparation of Carboxymethyl Cellulose (CMC) Aqueous Solution 4-2]
[0486] 1.5 mass % of commercially available carboxymethyl cellulose and 98.5 mass % of distilled water were mixed and stirred at a rotation speed of 500 rpm for 10 minutes using a homodispersor to prepare a CMC aqueous solution 4-2. The CMC aqueous solution 4-2 was measured using a TVE-35H E-type viscometer from Toki Sangyo Co., Ltd. at a shear rate of 1,000 s -1The viscosity under the conditions was measured. As a result, the viscosity (ηb) was 2,575 mPa·s and the TI value was 6.5.
[0487] [Preparation of Carbon Nanotube Dispersion Liquid]
[0488] 0.400 mass % of commercially available single-walled carbon nanotubes, 0.600 mass % of carboxymethyl cellulose (CMC1) as a dispersant, and 99.000 mass % of distilled water were mixed and dispersed using a thin film gyratory high-speed mixer FILMIX manufactured by PRIMIX at a peripheral speed of 17 m / s to prepare a carbon nanotube dispersion.
[0489] [Manufacturing of Positive Electrode Precursor 4-1]
[0490] Activated carbon 4-1: 56.425 mass % as a positive electrode active material, lithium carbonate 30.000 mass % as an alkali metal compound, carbon black 5.000 mass % as a conductive material, acrylic latex (LTX) 4.500 mass % as a binder, CMC aqueous solution 4-1 in an amount corresponding to 2.000 mass % of CMC content as dispersant 1, PVP (polyvinyl pyrrolidone) 2.000 mass % as dispersant 2, and the above carbon nanotube dispersion in an amount corresponding to 0.030 mass % of carbon nanotube content were added, and distilled water was further mixed so that the mass ratio of the solid content was 36.0%, and the mixture was dispersed at a rotation speed of 2,000 rpm for 10 minutes using an auto-rotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky Co., Ltd. to obtain a positive electrode coating solution 4-1. In addition, dispersant 3 in Table 9 shows the amount of CMC contained in the carbon nanotube dispersion.
[0491] The viscosity curve of the positive electrode coating liquid 4-1 was measured using MCR102 manufactured by Anton-Paar. Figure 3 The viscosity curve of the positive electrode coating liquid 4-1 is shown in FIG. -1 In the range of , the viscosity does not decrease monotonically with increasing shear rate. In addition, X / Y is calculated to be 3.49.
[0492] The positive electrode coating liquid 4-1 was applied to one side of an aluminum foil having a thickness of 15 μm using a doctor blade, dried on a hot plate heated to 50° C. for 10 minutes, and then pressed using a roller press at a pressure of 6 kN / cm and a surface temperature of 25° C. to obtain a positive electrode precursor 4-1.
[0493] The total thickness of the positive electrode precursor 4-1 obtained was measured at any 10 locations using a Linear Gauge Sensor GS-551 manufactured by Ono Keiki Co., Ltd. The thickness of the positive electrode active material layer was calculated by subtracting the thickness of the aluminum foil from the average value. The thickness of the positive electrode active material layer of the positive electrode precursor 4-1 was 83.6 μm. In addition, the positive electrode basis weight was 51.6 g / m 2 , so the bulk density is 0.617 g / cc.
[0494] [Manufacturing of positive electrode coating liquid and positive electrode precursors 4-2 to 4-10]
[0495] The types and amounts of each component were as shown in Table 9 below, and positive electrode coating liquids 4-2 to 4-10 and positive electrode precursors 4-2 to 4-10 were prepared in the same manner as in [Preparation of positive electrode precursor 4-1]. At this time, the viscosity curves of positive electrode coating liquids 4-2 to 4-10 were measured in the same manner as in positive electrode coating liquid 4-1, and the presence or absence of monotonic decrease in viscosity was confirmed, and the value of X / Y was calculated. Figure 4 , Figure 5 , Figure 6 The viscosity curves of positive electrode coating solutions 4-4, 4-7, and 4-10 are shown respectively.
[0496] [Table 9]
[0497] Table 9
[0498]
[0499] [Manufacturing Example of Negative Electrode]
[0500] 82.8% by mass of artificial graphite, 4.3% by mass of porous carbon, 8.7% by mass of acetylene black, 2.0% by mass of CMC (carboxymethyl cellulose), 2.2% by mass of SBR (styrene-butadiene rubber) latex, and distilled water with a solid content of 34.0% by mass are mixed to obtain a mixture thereof. The obtained mixture is dispersed at a rotation speed of 2,000 rpm for 10 minutes using an autorotation-revolution mixer "Awatori Rentaro (registered trademark)" manufactured by Thinky to obtain a negative electrode coating liquid 4-1. The negative electrode coating liquid 4-1 is applied to one side of an electrolytic copper foil having a thickness of 8 μm using a scraper and dried for 10 minutes on a hot plate heated to 50°C. Next, a roller press is used to press at a pressure of 5 kN / cm and a surface temperature of 25°C at the pressing portion to produce a negative electrode 4-1. The total thickness of the negative electrode 4-1 was measured at 10 random locations using a film thickness meter "Linear Gauge Sensor GS-551" manufactured by Ono Keiki Co., Ltd., and the thickness of the negative electrode active material layer was determined by subtracting the thickness of the electrolytic copper foil from the average value. The thickness of the negative electrode active material layer of the negative electrode 4-1 was 30 μm.
[0501] [Example of Preparation of Electrolyte Solution]
[0502] A mixed solvent of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl methyl carbonate (DMC) = 34:22:44 (volume ratio) was used as an organic solvent, and the electrolyte salt was dissolved in a manner such that the concentration ratio of LiPF6 to LiFSI was 3:1 and the total concentration was 1.2 mol / L to obtain a non-aqueous electrolyte solution 4-1.
[0503] 《Example 4-1》
[0504] <Manufacturing of non-aqueous lithium storage element>
[0505] [Assembly]
[0506] Cut the positive electrode precursor 4-1 into a piece of 4.4cm×9.4cm in size with the positive electrode active material layer. Then cut the negative electrode 4-1 into a piece of 4.5cm×9.5cm in size with the negative electrode active material layer. Also prepare a 4.7cm×9.8cm polyethylene separator (manufactured by Asahi Kasei, thickness 15μm). Using these parts, stack the positive electrode active material layer and the negative electrode active material layer opposite to each other with the separator sandwiched in the order of the positive electrode precursor 4-1, the separator, and the negative electrode 4-1 to obtain an electrode laminate. Ultrasonic weld the positive terminal and the negative terminal on the obtained electrode body, load it into an outer body formed by an aluminum laminate packaging material, and seal the three sides including the electrode terminal portion by heat sealing. In this way, a non-aqueous lithium storage element 4-1 is produced.
[0507] [Injection]
[0508] Under atmospheric pressure, in a dry air environment with a temperature of 25°C and a dew point of -40°C or less, about 3.0g of non-aqueous electrolyte 4-1 is injected into the outer body containing the non-aqueous lithium storage element 4-1 manufactured as described above. Next, the outer body containing the electrode laminate and the non-aqueous electrolyte is placed in a decompression chamber, and after the pressure is reduced from atmospheric pressure to -87kPa, it is returned to atmospheric pressure and allowed to stand for 5 minutes. Thereafter, after the outer body in the chamber is decompressed from atmospheric pressure to -87kPa, it is returned to atmospheric pressure, and after the process is repeated 4 times, it is allowed to stand at atmospheric pressure for 15 minutes. The non-aqueous electrolyte 4-1 is impregnated into the electrode laminate by the above process. Thereafter, the electrode laminate impregnated with the non-aqueous electrolyte 4-1 is placed in a decompression sealing machine, and sealed at a pressure of 0.1MPa for 10 seconds at 180°C under a state of decompression to -95kPa, thereby sealing the outer body.
[0509] [Alkali metal doping process]
[0510] Next, the nonaqueous lithium storage element 4-1 was placed in a thermostatic chamber set at 45°C. A charge-discharge device manufactured by Asuka Electronics Co., Ltd. was used, and the current value per electrode area of the positive electrode was 1.2 mA / cm 2 After constant current charging was performed until the voltage reached 4.5 V, constant voltage charging at 4.5 V was continued for 3 hours. This method was used to perform initial charging and alkali metal doping. Thereafter, the charge-discharge cycle consisting of the following discharge step and charge step was repeated 5 times. In the discharge step, the current value per electrode area of the positive electrode was 1.2 mA / cm 2 The battery was discharged from 4.0V to 2.0V and then discharged at 2.0V for 10 minutes. During the charging process, the current value per electrode area of the positive electrode was 1.2mA / cm 2 The battery was charged from 2.0V to 4.0V with constant current and then continued to charge at 4.0V for 10 minutes.
[0511] [Aging process]
[0512] The nonaqueous lithium storage element 4-1 after the alkali metal doping step was placed in a thermostatic chamber set at 60°C and the current value per electrode area of the positive electrode was 1.2 mA / cm 2 After constant current charging to 4.0 V, constant voltage charging at 4.0 V was performed for 16 hours.
[0513] [Exhaust process]
[0514] For the non-aqueous lithium storage element 4-1 after the aging process, a portion of the aluminum laminated packaging material is unsealed under an argon environment with a temperature of 25°C and a dew point of -60°C. Next, a partially opened aluminum laminated packaging material containing an electrode stack is placed in a decompression chamber, and a diaphragm pump is used to reduce the pressure from atmospheric pressure to -80kPa in 3 minutes, and then restored to atmospheric pressure in 3 minutes, and the process is repeated a total of 10 times. Thereafter, the partially opened aluminum laminated packaging material containing the electrode stack is placed in a decompression sealer, and after reducing the pressure to -90kPa, it is sealed at 200°C with a pressure of 0.1MPa for 10 seconds, thereby sealing the aluminum laminated packaging material to make a non-aqueous lithium storage element.
[0515] <Evaluation of non-aqueous lithium storage element>
[0516] [Measurement of internal resistance Ra]
[0517] The internal resistance Ra of the obtained nonaqueous lithium storage element 4-1 was measured by the above method in a thermostatic chamber set at 25° C. using a charge and discharge device (5 V, 10 A) manufactured by Asuka Electronics Co., Ltd. The result was 119 mΩ.
[0518] 《Examples 4-2 to 4-5, Comparative Examples 4-1 to 4-5》
[0519] A nonaqueous lithium storage element was prepared in the same manner as in Example 4-1 except that positive electrode precursors 4-2 to 4-10 were used. The evaluation results are shown in Table 10. By adding carbon nanotubes in this way, the positive electrode coating liquid has appropriate viscosity characteristics, thereby achieving both bulk density and internal resistance.
[0520] [Table 10]
[0521] Table 10
[0522]
[0523] Industrial Applicability
[0524] Using the non-aqueous lithium storage element of the present invention, for example, by connecting multiple non-aqueous lithium storage elements in series or in parallel, a storage module can be made. The non-aqueous lithium storage element of the present invention and the above-mentioned storage module can be appropriately used in various storage systems, for example: a power regeneration system of a hybrid drive system of an automobile requiring high-load charge and discharge cycle characteristics; a power load balancing system in natural power generation such as solar power generation, wind power generation, or microgrids; an uninterruptible power supply system in a factory's production equipment, etc.; a non-contact power supply system for the purpose of balancing and storing voltage fluctuations such as microwave power transmission and electric field resonance; and an energy harvesting system for the purpose of using power generated by vibration power generation, etc.; electric vehicles, plug-in hybrid vehicles, electric two-wheeled vehicles, hub motor systems, and electric power steering systems as vehicle power sources; a fast charging system for charging at a high current in order to charge in a short time. The non-aqueous lithium storage element of the present invention can maximize the effect of the present invention when used as a lithium ion capacitor or a lithium ion secondary battery, so it is preferred.
[0525] Explanation of symbols
[0526] 1 Negative electrode active material
[0527] 2 Bundled single-walled carbon nanotubes
[0528] 3 Bridging based on bundled single-walled carbon nanotubes
[0529] 4 Positive electrode active material
Claims
1. A non-aqueous alkali metal storage element comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte containing alkali metal ions, wherein: The positive electrode comprises a positive electrode current collector and a positive electrode active material layer provided on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material having activated carbon as a main component and carbon nanotubes. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer provided on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and carbon nanotubes. The carbon nanotubes are single-layer carbon nanotubes having a bundle structure with an average fiber diameter of 5 nm to 20 nm. When the content of carbon nanotubes contained in the positive electrode active material layer is A, and the content of carbon nanotubes contained in the negative electrode active material layer is B, and the units of A and B are mass %, 0.010≤A≤0.200、 0.003≤B≤0.120, and A>B.
2. The nonaqueous alkali metal energy storage device according to claim 1, wherein The carbon nanotubes cover the surface of the positive electrode active material in a mesh shape.
3. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The carbon nanotubes bridge the positive electrode active materials.
4. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The carbon nanotubes cover the surface of the negative electrode active material in a mesh shape.
5. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The carbon nanotubes bridge the negative electrode active materials.
6. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The amount of copper element contained in the positive electrode active material layer is 1 ppm or more and 500 ppm or less.
7. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The non-aqueous electrolyte solution comprises a phosphate amide represented by the following general formula (1): [Chemistry 1] In the formula, m represents an integer of 1 or 2, R 1 and R 2 independently represent a branched or straight-chain alkyl group having 1 to 6 carbon atoms, or a branched or straight-chain hydrocarbon group having an unsaturated bond; wherein R 1 and R 2 each independently has a substituent selected from the group consisting of an alkylthio group and a saturated heterocyclic group, or has no substituent, R 1 With R 2 Bonded to each other to form a 5- to 8-membered ring structure or not bonded to form a ring; R 3 It represents a branched or linear alkyl group having 1 to 6 carbon atoms or a branched or linear fluorine-containing alkyl group having 1 to 6 carbon atoms.
8. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: Regarding the activated carbon in the positive electrode active material, when the mesopore volume derived from pores with a diameter of 20 Å or more and 500 Å or less, calculated by the BJH method, is designated as V1, the micropore volume derived from pores with a diameter of less than 20 Å, calculated by the MP method, is designated as V2, and the units of V1 and V2 are cc / g, 0.3 < V1 ≤ 0.8 and 0.5 ≤ V2 ≤ 1.0 are satisfied, and the specific surface area measured by the BET method is 1,500 m 2 / g or more and 3,000 m 2 / g or less.
9. The nonaqueous alkali metal energy storage device according to claim 8, wherein The ratio V1 / V2 of the mesopore volume V1 to the micropore volume V2 is in the range of 0.3≤V1 / V2≤0.
9.
10. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: Regarding the activated carbon in the positive electrode active material, when the mesopore volume derived from pores with a diameter of 20 Å or more and 500 Å or less, calculated by the BJH method, is set as V1, the micropore volume derived from pores with a diameter of less than 20 Å, calculated by the MP method, is set as V2, and the units of V1 and V2 are cc / g, 0.8 < V1 ≤ 2.5 and 0.8 < V2 ≤ 3.0 are satisfied, and the specific surface area measured by the BET method is 2,300 m 2 / g or more and 4,000 m 2 / g or less.
11. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The thickness of the positive electrode active material layer is 30 μm or more and 100 μm or less per single side of the positive electrode current collector.
12. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The negative electrode active material comprises a composite carbon material, In the composite carbon material, the mass ratio of the carbonaceous material to the graphite material is 2 mass % or more and 5 mass % or less.
13. The nonaqueous alkali metal energy storage device according to claim 12, wherein The doping amount of lithium ions per unit mass of the composite carbon material is greater than or equal to 100 mAh / g and less than or equal to 550 mAh / g.
14. The nonaqueous alkali metal energy storage device according to claim 1 or 2, wherein: The thickness of the negative electrode active material layer is 15 μm or more and 60 μm or less per single side of the negative electrode current collector. 15 . A power storage module comprising the nonaqueous alkali metal power storage element according to claim 1 .
16. The power storage module according to claim 15, wherein: The power storage module is assembled into a system selected from the group consisting of a power regeneration assist system, a power load balancing system, an uninterruptible power supply system, a contactless power supply system, an energy harvesting system, a natural energy storage system, an electric power steering system, an emergency power supply system, a hub motor system, an idle stop system, an electric vehicle, a plug-in hybrid vehicle, an electric two-wheeler, a fast charging system and a smart grid system.
17. A positive electrode coating solution comprising activated carbon, an alkali metal compound, and a single-walled carbon nanotube, wherein: The amount of solid content is 35.0 mass % or more and 50.0 mass % or less relative to the total mass of the positive electrode coating liquid, The amount of the single-walled carbon nanotubes contained in the positive electrode coating solution is 0.010 mass % or more and 0.200 mass % or less based on the total mass of the solid content contained in the positive electrode coating solution. Satisfies either or both of the following (a) and (b), (a) At a shear rate of 10 s -1 More than 1000s -1 In the following range, the viscosity decreases monotonically with increasing shear rate; (b) At a shear rate of 100 s -1 More than 1000s -1 In the following range, the ratio X / Y of the maximum value X of the viscosity to the minimum value Y of the viscosity is 1.0 or more and 4.0 or less, and the units of X and Y are mPa·s.
18. The positive electrode coating solution according to claim 17, wherein The positive electrode coating solution contains a compound containing copper atoms.
Citation Information
Patent Citations
Negative electrode for lithium ion secondary battery and for lithium ion capacitor
JP2015156293A
Electrode for electricity storage devices, electricity storage device, and method for producing electrode for electricity storage devices
WO2013073526A1
METHOD FOR STABILIZING LiPF 6, ELECTROLYTE SOLUTION FOR NONAQUEOUS SECONDARY BATTERIES HAVING EXCELLENT THERMAL STABILITY, AND NONAQUEOUS SECONDARY BATTERY HAVING EXCELLENT THERMAL STABILITY
WO2013187073A1
Nonaqueous electrolyte solution for batteries and lithium secondary battery
WO2017038406A1
Positive electrode precursor
WO2017126687A1